Crosslinked resin particles and method for producing the same

The production of biodegradable crosslinked resin particles using PHA resins addresses the lack of such technology, enhancing mechanical properties and environmental sustainability by creating particles that are effectively biodegradable and suitable for various resin applications.

JP2025063459APending Publication Date: 2025-04-16KANEKA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023172673
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

There is currently no technology for producing biodegradable crosslinked resin particles, which are essential for improving mechanical strength and environmental sustainability in resin products.

Method used

The development of crosslinked resin particles using biodegradable resins, specifically polyhydroxyalkanoate (PHA) resins, with a gel fraction of 50% or more, a volume average particle size of 0.10 μm to 10.00 μm, and a glass transition temperature of 0°C or less, which are crosslinked using peroxides in an aqueous dispersion.

Benefits of technology

This solution provides novel biodegradable crosslinked resin particles that enhance the impact resistance and tear strength of molded products while promoting environmental sustainability by facilitating biodegradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063459000001
    Figure 2025063459000001
  • Figure 2025063459000002
    Figure 2025063459000002
  • Figure 2025063459000003
    Figure 2025063459000003
Patent Text Reader

Abstract

To provide novel crosslinked resin particles having biodegradability and a method for producing the same.SOLUTION: Provided are crosslinked resin particles containing a polyhydroxyalkanoate resin and having a gel fraction of 50% or more, a volume average particle diameter of 0.1 μm to 10 μm or a median diameter of 0.10 μm to 10.00 μm, and a glass transition temperature of 0°C or lower.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to crosslinked resin particles and a method for producing the same. [Background technology]

[0002] 2. Description of the Related Art Conventionally, techniques for adding various modifiers (for example, crosslinked particles) to thermoplastic resins in order to improve the mechanical strength, such as the impact strength, of thermoplastic resins have been known.

[0003] Known examples of crosslinked resin particles include crosslinked resin particles made of resins such as acrylic resins, acrylic silicone resins, and polystyrene (see, for example, Patent Documents 1 and 2).

[0004] Meanwhile, in recent years, from the viewpoint of consideration for the environment during and after the disposal of resin products, there has been active development of biodegradable resins (hereinafter, sometimes referred to as "biodegradable resins"). For example, Patent Document 3 describes crosslinking of poly(3-hydroxyalkanoate), a type of biodegradable resin, by melt-kneading the resin in the presence of an organic peroxide. However, it describes that the crosslinked resin produced by such melt-kneading is used to constitute a film and / or sheet, and there is no description at all about producing small crosslinked resin particles. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2009-56770 A [Patent Document 2] JP 2003-82191 A [Patent Document 3] International Publication No. 2019 / 022008 Summary of the Invention [Problem to be solved by the invention]

[0006] So far, no biodegradable crosslinked resin particles have been known.

[0007] An embodiment of the present invention has been made in consideration of the above-mentioned current situation, and an object of the invention is to provide novel crosslinked resin particles having biodegradability. [Means for solving the problem]

[0008] Means of the Invention As a result of intensive research into solving the above problems, the present inventors have succeeded in producing novel crosslinked resin particles using a biodegradable resin, thereby completing one embodiment of the present invention.

[0009] That is, one embodiment of the present invention includes the following configuration.

[0010] [1] Crosslinked resin particles comprising a biodegradable resin (A), having a gel fraction of 50% or more, a volume average particle diameter of 0.10 μm to 10.00 μm or a median diameter of 0.10 μm to 10.00 μm, and a glass transition temperature of 0° C. or lower.

[0011] [2] The crosslinked resin particles according to [1], wherein the biodegradable resin (A) is a polyhydroxyalkanoate-based resin.

[0012] [3] The crosslinked resin particles according to [2], wherein the polyhydroxyalkanoate resin is a poly(3-hydroxyalkanoate) resin.

[0013] [4] The crosslinked resin particles according to any one of [1] to [3], wherein the crosslinked resin particles are crosslinked using a peroxide.

[0014] [5] The crosslinked resin particles according to [4], wherein the crosslinked resin particles are crosslinked in the presence of the peroxide and a polyfunctional compound.

[0015] [6] The crosslinked resin particles according to any one of [1] to [5], wherein the crosslinked resin particles are not foamed.

[0016] [7] The crosslinked resin particles according to any one of [1] to [6], wherein the proportion of the biodegradable resin (A) in the crosslinked resin particles is 80% by weight or more.

[0017] [8] The crosslinked resin particles according to any one of [1] to [7], wherein the gel fraction is 70% to 100%.

[0018] [9] An aqueous dispersion in which the crosslinked resin particles according to any one of [1] to [8] are dispersed in an aqueous medium.

[0019]

[10] Thermoplastic resin, and A thermoplastic resin composition comprising the crosslinked resin particles according to any one of [1] to [8].

[0020]

[11] The thermoplastic resin composition according to

[10] , wherein the thermoplastic resin contains a biodegradable resin (B).

[0021]

[12] The thermoplastic resin composition according to

[10] or

[11] , wherein the biodegradable resin (B) contains a polyester-based resin.

[0022]

[13] The thermoplastic resin composition according to any one of

[10] to

[12] , further comprising a crystal nucleating agent and / or a lubricant.

[0023]

[14] A molded article obtained by molding the thermoplastic resin composition according to any one of

[10] to

[13] .

[0024]

[15] The molded article according to

[14] , which is a sheet molded article, a film molded article, a blow molded article, an extrusion molded article, a vacuum molded article, or an injection molded article.

[0025]

[16] A modifier for thermoplastic resins, comprising crosslinked resin particles, the crosslinked resin particles comprising a biodegradable resin (A), having a gel fraction of 50% or more, a volume average particle diameter of 0.10 μm to 10.00 μm or a median diameter of 0.10 μm to 10.00 μm, and a glass transition temperature of 0° C. or lower.

[0026]

[17] A method for producing the crosslinked resin particles according to any one of [1] to [8], comprising a step of crosslinking the biodegradable resin (A) particles in an aqueous dispersion of the biodegradable resin (A) particles in the presence of a peroxide. Effect of the Invention

[0027] According to one embodiment of the present invention, it is possible to provide a novel crosslinked resin particle having biodegradability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each configuration described below, and various modifications are possible within the scope of the claims. In addition, embodiments or examples obtained by combining the technical means disclosed in different embodiments or examples are also included in the technical scope of the present invention. Furthermore, new technical features can be formed by combining the technical means disclosed in each embodiment. All academic documents and patent documents described in this specification are incorporated herein by reference. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more (including A and greater than A) and B or less (including B and smaller than B)".

[0029] [1. Crosslinked resin particles] The crosslinked resin particles according to one embodiment of the present invention contain a biodegradable resin (A), have a gel fraction of 50% or more, a volume average particle diameter of 0.10 μm to 10.00 μm or a median diameter of 0.10 μm to 10.00 μm, and a glass transition temperature of 0° C. or lower.

[0030] In this specification, "glass transition temperature" may be referred to as "Tg", and "crosslinked resin particles according to one embodiment of the present invention" may be referred to as "the present crosslinked resin particles".

[0031] The crosslinked resin particles have the advantage of being biodegradable because they contain a biodegradable resin (A). Therefore, they are expected to be useful as crosslinked resin particles that address the problem of plastic waste and are environmentally friendly. In addition, since the crosslinked resin particles are biodegradable, the resin composition and molded article containing the crosslinked resin particles can suppress soil pollution due to disposal. This can contribute to the achievement of the Sustainable Development Goals (SDGs), such as Goal 12 "Ensure sustainable consumption and production patterns." Furthermore, when the biodegradable resin (A) is marine degradable in addition to soil degradable, the resin composition and molded article containing the crosslinked resin particles can suppress marine pollution in addition to suppressing soil pollution due to disposal.

[0032] In a preferred embodiment of the present invention, a molded article obtained by molding a resin composition containing the present crosslinked resin particles and a thermoplastic resin has an advantage of being excellent in tensile impact strength. In a further preferred embodiment of the present invention, a molded article obtained by molding a resin composition containing the present crosslinked resin particles and a thermoplastic resin has an advantage of being excellent in tear strength.

[0033] <Biodegradable resin (A)> The biodegradable resin (A) is not particularly limited as long as it is a resin having biodegradability. Examples of the biodegradable resin include aliphatic polyesters and aliphatic aromatic polyesters.

[0034] Examples of the aliphatic polyesters include (i) polyhydroxyalkanoate resins (hereinafter, sometimes referred to as "PHA"), (ii) polylactic acid (hereinafter, sometimes referred to as "PLA"), (iii) polycaprolactone (hereinafter, sometimes referred to as "PCL"), and (iv) aliphatic polyesters other than PHA, PLA, and PCL.

[0035] "PHA" is a general term for polymers containing hydroxyalkanoic acid as a monomer unit (monomer repeating unit), and is generally biodegradable. PHA is an aliphatic polyester, preferably a polyester not containing an aromatic ring. In this specification, "PHA" refers to a polymer containing hydroxyalkanoic acid repeating units in an amount of 50 mol% or more of all monomer repeating units (100 mol%). PHA preferably contains hydroxyalkanoic acid repeating units in an amount of 60 mol% or more, more preferably 70 mol% or more, of all monomer repeating units (100 mol%).

[0036] There is no particular limitation on the PHA. Examples of PHA include polyglycolic acid, poly(3-hydroxyalkanoate)-based resin (hereinafter sometimes referred to as "P3HA"), poly(4-hydroxyalkanoate)-based resin, and the like. As the PHA, only one type may be used alone, or two or more types may be used in combination. The PHA preferably contains a poly(3-hydroxyalkanoate)-based resin, and more preferably is a poly(3-hydroxyalkanoate)-based resin (in other words, composed only of a poly(3-hydroxyalkanoate)-based resin).

[0037] In this specification, "polyglycolic acid" refers to a resin containing 50 mol % or more of repeating units represented by [-CH2-CO-O-] out of all monomer repeating units (100 mol %). Polyglycolic acid may contain 60 mol % or more, 70 mol % or more, 80 mol % or more, or 90 mol % or more of repeating units represented by [-CH2-CO-O-] out of all monomer repeating units (100 mol %).

[0038] The polyglycolic acid may be a homopolymer of glycolic acid, or a copolymer of glycolic acid and a monomer other than glycolic acid (for example, a copolymer of glycolic acid and lactic acid, a copolymer of glycolic acid and caprolactone, etc.).

[0039] Polyglycolic acid can be obtained by known methods such as condensation polymerization of glycolic acid and ring-opening polymerization of glycolide.

[0040] The P3HA is a 3-hydroxyalkanoic acid repeating unit represented by the formula: [-CHR-CH2-CO-O-] (wherein R is C n H 2n+1 where n is an integer of 1 or more and 15 or less.) is a polyhydroxyalkanoate containing the 3-hydroxyalkanoic acid repeating unit as an essential repeating unit. In this specification, "P3HA" refers to a resin containing 50 mol % or more of the 3-hydroxyalkanoic acid repeating unit out of all monomer repeating units (100 mol %). The P3HA preferably contains 60 mol % or more, and more preferably 70 mol % or more of the 3-hydroxyalkanoic acid repeating unit out of all monomer repeating units (100 mol %).

[0041] P3HA is not particularly limited, and may be a homopolymer containing the repeating unit described above, or a copolymer containing the repeating unit described above. Examples of the copolymer include copolymers of 3-hydroxybutanoic acid (hereinafter sometimes referred to as "3HB") and one or more monomers selected from the group consisting of 3-hydroxypropionic acid, 3-hydroxypentanoic acid, 3-hydroxyhexanoic acid, 3-hydroxyheptanoic acid, 3-hydroxyoctanoic acid, 3-hydroxynonanoic acid, 3-hydroxydecanoic acid, 3-hydroxyundecanoic acid, 3-hydroxydodecanoic acid, 3-hydroxytridecanoic acid, 3-hydroxytetradecanoic acid, 3-hydroxyhexadecanoic acid, and 3-hydroxyoctadecanoic acid. Alternatively, another example of the copolymer may be, for example, a copolymer of 3HB and one or more monomers selected from the group consisting of 4-hydroxybutanoic acid, 4-hydroxypentanoic acid, 4-hydroxyhexanoic acid, 4-hydroxyheptanoic acid, 4-hydroxyoctanoic acid, 4-hydroxynonanoic acid, 4-hydroxydecanoic acid, 4-hydroxyundecanoic acid, 4-hydroxydodecanoic acid, 4-hydroxytridecanoic acid, 4-hydroxytetradecanoic acid, 4-hydroxyhexadecanoic acid, and 4-hydroxyoctadecanoic acid.

[0042] Examples of P3HA include poly(3-hydroxybutyrate) (hereinafter, sometimes referred to as "P3HB"), which is a homopolymer of 3HB, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (hereinafter, sometimes referred to as "P3HB3HH"), and poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (hereinafter, sometimes referred to as "P3HB4HB"). Only one type of P3HA may be used, or two or more types may be used in combination. In this specification, "poly(X-co-Y)" refers to a copolymer containing X repeating units and Y repeating units, and is intended to mean a copolymer obtained by copolymerizing a monomer from which the X repeating units are derived and a monomer from which the Y repeating units are derived. In addition, during the production of P3HA by a microorganism, a small amount (about 1 mol% or less) of a monomer may be copolymerized, but if it does not significantly affect the physical properties of the obtained P3HA, the monomer is considered to be not copolymerized, and the product is called by a name that does not include the monomer.

[0043] P3HA can be produced by microorganisms. Such microbially produced P3HA is usually P3HA composed only of D-form (R-form) 3-hydroxyalkanoic acid repeating units. Among the microbially produced P3HA, P3HB, P3HB3HH and P3HB4HB are more preferred, and P3HB3HH and P3HB4HB are even more preferred, because they are easy to produce industrially.

[0044] It is also preferred that P3HA contains a 3-hydroxybutanoic acid (3HB) repeating unit. When P3HA contains a 3HB repeating unit, the composition ratio of the 3HB repeating unit in the total monomer repeating units (100 mol%) is preferably 60 mol% to 99 mol%, more preferably 61 mol% to 97 mol%, and even more preferably 62 mol% to 95 mol%, from the viewpoint of the balance between flexibility and strength. When the composition ratio of the 3HB repeating unit in P3HA is 60 mol% or more, there is an advantage that the rigidity of the crosslinked resin particles can be further improved. On the other hand, when the composition ratio of the 3HB repeating unit in P3HA is 99 mol% or less, there is an advantage that the flexibility of the crosslinked resin particles tends to be further improved. The monomer composition ratio of P3HA can be measured by gas chromatography or the like (for example, see International Publication No. 2014 / 020838). As P3HA, two or more types having different composition ratios of the 3HB repeating unit may be used in combination.

[0045] Microorganisms that produce P3HA are not particularly limited as long as they have the ability to produce P3HA. For example, the first P3HB-producing bacterium was Bacillus megaterium, discovered in 1925, and other natural microorganisms such as Cupriavidus necator (formerly classified as Alcaligenes eutrophus and Ralstonia eutropha) and Alcaligenes latus are also known. In these microorganisms, P3HB accumulates within the bacterial cells.

[0046] Also, as producers of copolymers of 3HB and other hydroxyalkanoic acids, Aeromonas caviae, which produces P3HB3HH, and Alcaligenes eutrophus, which produces poly(3-hydroxybutyrate-co-4-hydroxybutyrate), are known. In particular, in order to increase the productivity of P3HB3HH, Alcaligenes eutrophus AC32 (FERM BP-6038) (T. Fukui, Y. Doi, J. Bateriol., 179, p4821-4830 (1997)) into which genes of P3HA synthase group have been introduced is preferred. Microorganisms that have been cultured under appropriate conditions to accumulate P3HA in the cells are used. In addition to the above, genetically modified microorganisms into which various P3HA synthesis-related genes have been introduced may be used depending on the P3HA to be produced, and culture conditions, including the type of substrate, may be optimized.

[0047] The PHA may have a glass transition temperature of 0° C. or lower, may have a glass transition temperature of more than 0° C., or may be a mixture of a PHA having a glass transition temperature of 0° C. or lower and a PHA having a glass transition temperature of more than 0° C. From the viewpoint of making the glass transition temperature of the crosslinked resin particles 0° C. or lower, for example, the PHA contained in the crosslinked resin particles preferably contains a PHA having a glass transition temperature of 0° C. or lower. The PHA contained in the crosslinked resin particles preferably contains 60% by weight or more of PHA having a glass transition temperature of 0° C. or lower, more preferably 70% by weight or more, even more preferably 80% by weight or more, and particularly preferably 90% by weight or more, of the total PHA contained in the crosslinked resin particles (100% by weight).

[0048] The glass transition temperature of a biodegradable resin (A) (e.g., PHA) is determined as the midpoint between the temperatures at which a baseline shift begins and ends when 2 to 3 mg of PHA is filled into an aluminum pan, heated in a differential scanning calorimeter from -80°C to 180°C at a rate of 10°C / min under a nitrogen stream until the resin is completely melted, cooled from 180°C to -80°C at a rate of 10°C / min, and then heated again from -80°C to 180°C at a rate of 10°C / min.

[0049] The weight average molecular weight of the PHA is not particularly limited. The weight average molecular weight of the PHA is preferably 50,000 to 3,000,000, preferably 100,000 to 2,000,000, and more preferably 150,000 to 1,500,000. When the weight average molecular weight of the PHA is 50,000 or more, it has an advantage that the tendency of the strength of the crosslinked resin particles to decrease can be reduced or avoided. Also / alternatively, when the weight average molecular weight of the PHA is 50,000 or more, it has an advantage that the tendency of the low molecular weight component to become sticky can be reduced or avoided. On the other hand, a PHA having a weight average molecular weight of 3,000,000 or less can have an advantage that the PHA is easy to manufacture and / or that the PHA is easy to handle in order to achieve the object of one embodiment of the present invention. The numerical value of the weight average molecular weight of the PHA is a value obtained by measuring the PHA before the crosslinking treatment.

[0050] The weight average molecular weight can be measured by using gel permeation chromatography (GPC) (Shimadzu Corporation's "High Performance Liquid Chromatograph 20A System"), polystyrene gel (Showa Denko KK's "KG 4A", "K-806M", etc.) as a column, and chloroform as a mobile phase. The weight average molecular weight can be determined as a molecular weight converted into polystyrene using a calibration curve obtained by measuring polystyrene with a known molecular weight by the same measurement method. In this case, the calibration curve can be created using polystyrene with weight average molecular weights of 31,400, 197,000, 668,000, and 1,920,000. As the column for the GPC, a column appropriate for measuring the molecular weight may be used.

[0051] In this specification, "polylactic acid" refers to a resin containing 50 mol% or more of repeating units represented by [-CHCH3-CO-O-] out of all monomer repeating units (100 mol%). Polylactic acid may contain 60 mol% or more, 70 mol% or more, 80 mol% or more, or 90 mol% or more of repeating units represented by [-CHCH3-CO-O-] out of all monomer repeating units (100 mol%).

[0052] As the polylactic acid, a conventionally known polylactic acid can be used. The polylactic acid may be crystalline polylactic acid, amorphous polylactic acid, or a mixture of crystalline polylactic acid and amorphous polylactic acid.

[0053] The polylactic acid may be a homopolymer of lactic acid, a copolymer of lactic acid and other monomers, or a blend of a homopolymer of lactic acid and a copolymer of lactic acid and other monomers.

[0054] Examples of the other monomers include aliphatic hydroxycarboxylic acids other than lactic acid, aliphatic polyhydric alcohols, aliphatic polycarboxylic acids, polyfunctional polysaccharides, and caprolactone.

[0055] The lactic acid raw material for producing polylactic acid is not particularly limited, and L-lactic acid, D-lactic acid, DL-lactic acid, or a mixture thereof, or L-lactide, D-lactide, meso-lactide, or a mixture thereof, etc. Lactic acid obtained by microbial fermentation from renewable raw materials derived from plants such as starch can be suitably used.

[0056] The method for producing polylactic acid is not particularly limited, and known methods such as dehydration condensation polymerization and ring-opening polymerization can be used.

[0057] The weight-average molecular weight of polylactic acid is not particularly limited, but is preferably 50,000 to 1,000,000, more preferably 70,000 to 700,000, and even more preferably 100,000 to 400,000. When the weight-average molecular weight of polylactic acid is 50,000 or more, the crosslinked resin particles, and the crosslinked resin particles and their molded bodies can obtain sufficient rigidity and / or strength. On the other hand, polylactic acid having a weight-average molecular weight of 1,000,000 or less can have the advantage that the polylactic acid is easy to produce and / or easy to handle in order to achieve the object of one embodiment of the present invention.

[0058] "Polycaprolactone" includes, but is not limited to, polymers obtained by ring-opening polymerization of ε-caprolactone. In one embodiment of the present invention, PCL obtained by other manufacturing methods can also be used. An organometallic catalyst can also be used to promote the polymerization of PCL. In this specification, "PCL" also includes copolymers of ε-caprolactone and monomers other than ε-caprolactone (e.g., lactide, glycolic acid, etc.).

[0059] PCL typically has a melting point of 50°C to 65°C, a crystallization temperature of 10°C to 30°C, and a glass transition point of -50°C to -60°C.

[0060] The weight-average molecular weight of PCL is preferably 30,000 to 500,000, more preferably 100,000 to 400,000. When the weight-average molecular weight of PCL is 30,000 or more, the present crosslinked resin particles, the crosslinked resin particles, and their molded articles can have sufficient rigidity and / or strength. When the weight-average molecular weight of PCL is 500,000 or less, there is an advantage that the present crosslinked resin particles can be easily processed.

[0061] Commercially available PCL products include, for example, Ingevity's "Capa6506" (powder, Mw=130,000), "Capa6500" (pellet, Mw=130,000), "Capa6806" (powder, Mw=230,000), "Capa6800" (pellet, Mw=230,000), and "FB100" (pellet, Mw=300,000, contains PCL crosslinked material).

[0062] Examples of the aliphatic polyester other than PHA include (i) polycaprolactone (PCL), (ii) polylactic acid (PLA), and (iii) aliphatic polyesters having a structure in which an aliphatic diol and an aliphatic dicarboxylic acid are polycondensed. Specific examples of the aliphatic polyesters having a structure in which an aliphatic diol and an aliphatic dicarboxylic acid are polycondensed include polyethylene succinate, polybutylene succinate (hereinafter sometimes referred to as "PBS"), polyhexamethylene succinate, polyethylene adipate, polybutylene adipate, polyhexamethylene adipate, polybutylene succinate adipate (hereinafter sometimes referred to as "PBSA"), polyethylene sebacate, and polybutylene sebacate.

[0063] In this specification, "PBS" refers to an aliphatic polyester copolymer synthesized by an esterification reaction and / or transesterification reaction, and a condensation polymerization reaction, between an aliphatic diol component mainly composed of 1,4-butanediol and an aliphatic dicarboxylic acid component mainly composed of a succinic acid component such as succinic acid and / or its derivatives.

[0064] PBS, for example, contains butylene succinate repeat units represented by [-CO-(CH2)2-CO-O-(CH2)4-O-].

[0065] PBS can be produced from petroleum or from non-petroleum-based materials (e.g., plants).

[0066] In this specification, "PBS" also includes a "PBS-based resin" which is a copolymer of the above-mentioned PBS with a monomer other than 1,4-butanediol and succinic acid (e.g., L-lactic acid and / or caprolactone).

[0067] Commercially available PBS can also be used, such as "BioPBS FZ71" and "BioPBS FZ91" manufactured by Mitsubishi Chemical Corporation.

[0068] In this specification, "PBSA" refers to an aliphatic polyester copolymer synthesized by an esterification reaction and a condensation polymerization reaction between an aliphatic diol component mainly composed of 1,4-butanediol, an aliphatic dicarboxylic acid component mainly composed of a succinic acid component such as succinic acid and / or its derivatives, and adipic acid.

[0069] As long as the effect of one embodiment of the present invention is achieved, PBSA may have, in addition to butanediol repeating units, succinic acid repeating units, and adipic acid repeating units, any diol repeating units other than butanediol, any dicarboxylic acid repeating units other than succinic acid and adipic acid, and / or hydroxyalkanoic acid repeating units. Examples of the optional diols include ethylene glycol, 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanediol, and 1,4-cyclohexanedimethanol. Examples of the optional dicarboxylic acids include suberic acid, sebacic acid, dodecanoic acid, succinic anhydride, and adipic anhydride.

[0070] In this specification, "PBSA" also includes "PBSA-based resins" which are copolymers of the above-mentioned PBSA with monomers other than 1,4-butanediol, succinic acid, and adipic acid (e.g., lactic acid, terephthalic acid, malic acid, sebacic acid, azelaic acid, etc.) within the scope that does not impair biodegradability.

[0071] Commercially available PBSA can also be used, such as "BioPBS FD72" and "BioPBS FD92" manufactured by Mitsubishi Chemical Corporation.

[0072] As the aliphatic polyester, one of the above-mentioned various resins may be used alone, or two or more of them may be used in combination. In addition, among the above-mentioned various resins, one of the above-mentioned resins may be used alone, or two or more of them may be used in combination.

[0073] Examples of the aliphatic aromatic polyester include aliphatic aromatic polyesters obtained using both an aliphatic compound and an aromatic compound as monomers (using both an aliphatic compound and an aromatic compound as monomers).

[0074] Examples of the aliphatic aromatic polyester include polybutylene adipate terephthalate (hereinafter sometimes referred to as "PBAT"), polybutylene sebacate terephthalate (hereinafter sometimes referred to as "PBSeT"), polybutylene azelate terephthalate (hereinafter sometimes referred to as "PBAzT"), polybutylene succinate terephthalate (hereinafter sometimes referred to as "PBST"), polybutylene succinate adipate terephthalate (hereinafter sometimes referred to as "PBSAT"), and the like.

[0075] As used herein, "PBAT" refers to a random copolymer of 1,4-butanediol with adipic acid and terephthalic acid.

[0076] The PBAT is not particularly limited, but a PBAT obtained by reacting (a) a mixture consisting essentially of 35 to 95 mol % of adipic acid or an ester-forming derivative thereof, or a mixture of these, and 5 to 65 mol % of terephthalic acid or an ester-forming derivative thereof, or a mixture of these (the sum of the individual mol % is 100 mol %), with (b) a mixture containing butanediol (wherein the molar ratio of (a) to (b) is 0.4:1 to 1.5:1), as described in JP-A-10-508640 and the like, is preferred.

[0077] In one embodiment of the present invention, instead of the 1,4-butanediol in the production of PBAT, glycol compounds such as ethylene glycol, propylene glycol, heptanediol, hexanediol, octanediol, nonanediol, decanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, glycerin, pentaerythritol, bisphenol A, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc. Also, in one embodiment of the present invention, instead of the adipic acid in the production of PBAT, dicarboxylic acids such as oxalic acid, succinic acid, azelaic acid, dodecanedioic acid, malonic acid, glutaric acid, cyclohexanedicarboxylic acid, terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, bis(p-carboxyphenyl)methane, anthracenedicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 5-sodium sulfoisophthalic acid, 5-tetrabutylphosphonium isophthalic acid, etc. may be used.

[0078] Commercially available PBAT can also be used, for example, "Ecoflex C1200" manufactured by BASF.

[0079] In this specification, "PBSeT" refers to a random copolymer of 1,4-butanediol, sebacic acid, and terephthalic acid. For each embodiment of PBSeT, the above embodiment of PBAT may be appropriately applied in which the portions "adipic acid" and "adipic acid or an ester-forming derivative thereof" are replaced with "sebacic acid" and "sebacic acid or an ester-forming derivative thereof," respectively.

[0080] Commercially available PBSeT can also be used. Examples of commercially available PBSeT include "Ecoflex FS blend C2200" (registered trademark) manufactured by BASF.

[0081] In this specification, "PBAzT" refers to a random copolymer of 1,4-butanediol, azelaic acid, and terephthalic acid. For each embodiment related to PBAzT, the above embodiment related to PBAT in which "adipic acid" and "adipic acid or an ester-forming derivative thereof" are replaced with "azelaic acid" and "azelaic acid or an ester-forming derivative thereof", respectively, can be appropriately used.

[0082] In this specification, "PBST" refers to the above-mentioned PBS into which a terephthalate unit has been introduced. More specifically, "PBST" refers to an aliphatic aromatic polyester copolymer synthesized by an esterification reaction between an aliphatic dicarboxylic acid component mainly composed of a succinic acid component such as succinic acid and / or its derivatives and terephthalic acid, and a condensation polymerization reaction.

[0083] In the present specification, "PBSAT" means a copolymer containing, among the aliphatic dicarboxylic acid residues, the residues of succinic acid:adipic acid:phthalic acid, preferably in a ratio of 70-90:5-15:5-15 mol %. Therefore, in order to produce PBSAT, for example, a method can be mentioned in which a dicarboxylic acid mixture containing succinic acid, adipic acid, and phthalic acid in the above ratio is esterified with 1,4-butanediol, an aliphatic glycol, in a molar ratio of 1:1.2-2.0, and then a condensation polymerization reaction is carried out. The reactive groups and reaction conditions used in the reaction can be appropriately adopted from those used in existing biodegradable resins such as PBS.

[0084] As the aliphatic aromatic polyester, one of the above-mentioned various resins may be used alone, or two or more of them may be used in combination. In addition, among the above-mentioned various resins, one of the above-mentioned resins may be used alone, or two or more of them may be used in combination.

[0085] The biodegradable resin (A) contained in the crosslinked resin particles may have a glass transition temperature of 0°C or lower, or may have a glass transition temperature of more than 0°C, or may be a mixture of a biodegradable resin (A) having a glass transition temperature of 0°C or lower and a biodegradable resin (A) having a glass transition temperature of more than 0°C. From the viewpoint of making the glass transition temperature of the crosslinked resin particles 0°C or lower, the biodegradable resin (A) contained in the crosslinked resin particles preferably contains a biodegradable resin (A) having a glass transition temperature of 0°C or lower. The biodegradable resin (A) contained in the crosslinked resin particles preferably contains 60% by weight or more of the biodegradable resin (A) having a glass transition temperature of 0°C or lower, more preferably 70% by weight or more, even more preferably 80% by weight or more, and particularly preferably 90% by weight or more, of the total biodegradable resin (A) contained in the crosslinked resin particles 100% by weight. The glass transition temperature of the resin can be easily measured by the method described in the section (Glass transition temperature (Tg)) in the section (Examples) below.

[0086] In general, PHA, PCL, PBS, PBSA, PBAT, PBSeT, PBAzT, PBST and PBSAT other than polyglycolic acid have a Tg of less than 0°C. PCL generally has a Tg of -50°C to -60°C. PBS generally has a Tg of -30°C to -40°C. PBSA generally has a Tg of -40°C to -50°C. PBAT generally has a Tg of -30°C to -40°C. PBSeT generally has a Tg of -20°C to -40°C. PBAzT generally has a Tg of -20°C to -40°C. PBST generally has a Tg of -20°C to -40°C. PBSAT generally has a Tg of -20°C to -40°C.

[0087] Generally, polyglycolic acid and PLA have a Tg of 0° C. or higher. Polyglycolic acid generally has a Tg of 35° C. to 40° C. PLA generally has a Tg of 55° C. to 65° C.

[0088] On the other hand, the glass transition temperature of a resin depends on the structural units that constitute the resin. Therefore, for example, polyglycolic acid, which is a copolymer of glycolic acid and caprolactone, may have a Tg of less than 0°C depending on the content of caprolactone. Also, polylactic acid, which is a copolymer of lactic acid and caprolactone, may have a Tg of less than 0°C depending on the content of caprolactone. Such polyglycolic acid having a glass transition temperature of less than 0°C and polylactic acid having a glass transition temperature of less than 0°C can also be considered as biodegradable resin (A).

[0089] For example, the Tg of a copolymer of 3HB and a monomer other than 3HB in P3HA may depend on the type and content ratio of the monomer other than 3HB in the copolymer. For example, P3HB3HH, which has 10 mol % or more of 3HH repeating units out of 100 mol % of P3HB3HH repeating units, has a Tg of less than 0° C. For example, P3HB4HB, which has 6 mol % or more of 4HB repeating units out of 100 mol % of P3HB4HB repeating units, has a Tg of less than 0° C.

[0090] As the biodegradable resin (A), one of the various resins described above may be used alone, or two or more may be used in combination. In addition, in the various resins described above, one of the resins described above may be used alone, or two or more may be used in combination. In relation to the above, the biodegradable resin (A) may be (i) composed of only one or more aliphatic polyesters, (ii) composed of only one or more aliphatic aromatic polyesters, (iii) composed of only a mixture of one or more aliphatic polyesters and one or more aliphatic aromatic polyesters, or (iv) composed of a mixture of one or more aliphatic polyesters, one or more aliphatic aromatic polyesters, and one or more resins other than aliphatic polyesters and aliphatic aromatic polyesters.

[0091] The biodegradable resin (A) preferably contains one or more selected from the group consisting of (i) poly(3-hydroxybutyrate-co-4-hydroxybutyrate), (ii) polycaprolactone, (iii) aliphatic polyesters having a structure obtained by polycondensation of an aliphatic diol and an aliphatic dicarboxylic acid, and (v) aliphatic aromatic polyesters, and more preferably is one or more selected from the group (consisting only of one or more selected from the group).

[0092] The present crosslinked resin particles preferably contain 60% by weight or more of biodegradable resin in 100% by weight of the resin component of the crosslinked resin particles, more preferably 70% by weight or more, even more preferably 80% by weight or more, and particularly preferably 90% by weight or more. The present crosslinked resin particles may contain 100% by weight of biodegradable resin in 100% by weight of the resin component of the crosslinked resin particles. In other words, the resin component of the present crosslinked resin particles may be composed only of biodegradable resin. Note that the "resin component of the crosslinked resin particles" refers to the resin that essentially constitutes the crosslinked resin particles, and does not include components that crosslink the molecular chains of the resin (e.g., structures derived from polyfunctional compounds) and residues of components used for crosslinking the molecular chains of the resin (e.g., unreacted peroxides, decomposition products of peroxides, unreacted polyfunctional compounds, etc.).

[0093] The proportion of PHA in the crosslinked resin particles is not particularly limited, but may be 50% by weight or more, preferably 70% by weight or more, more preferably 80% by weight or more, even more preferably 90% by weight or more, and particularly preferably 95% by weight or more, based on 100% by weight of the resin component. It may be 99% by weight or more. There is no particular upper limit, and it is sufficient if it is 100% by weight or less.

[0094] The present crosslinked resin particles preferably contain 60% by weight or more of the biodegradable resin (A) in 100% by weight of the resin component of the crosslinked resin particles, more preferably 70% by weight or more, even more preferably 80% by weight or more, and particularly preferably 90% by weight or more. The present crosslinked resin particles may contain 100% by weight of the biodegradable resin (A) in 100% by weight of the resin component of the crosslinked resin particles. In other words, the resin component of the present crosslinked resin particles may be composed only of the biodegradable resin (A).

[0095] One embodiment of the present invention may be configured such that the biodegradable resin (A) does not include crosslinked resin particles containing 50% by weight or more of P3HB3HH, does not include crosslinked resin particles containing 60% by weight or more, does not include crosslinked resin particles containing 70% by weight or more, does not include crosslinked resin particles containing 80% by weight or more, or does not include crosslinked resin particles containing 90% by weight or more. The crosslinked resin particles in one embodiment of the present invention may not include P3HB3HH, in other words, one embodiment of the present invention may be configured such that the crosslinked resin particles containing P3HB3HH are not included.

[0096] One embodiment of the present invention may be configured such that, as the biodegradable resin (A), crosslinked resin particles containing 50% by weight or more of P3HA are excluded, crosslinked resin particles containing 60% by weight or more are excluded, crosslinked resin particles containing 70% by weight or more are excluded, crosslinked resin particles containing 80% by weight or more are excluded, or crosslinked resin particles containing 90% by weight or more are excluded. The crosslinked resin particles in one embodiment of the present invention may not contain P3HA, in other words, one embodiment of the present invention may be configured such that crosslinked resin particles containing P3HA are excluded.

[0097] One embodiment of the present invention may be configured such that the biodegradable resin (A) does not include crosslinked resin particles containing 50% by weight or more of PHA, does not include crosslinked resin particles containing 60% by weight or more, does not include crosslinked resin particles containing 70% by weight or more, does not include crosslinked resin particles containing 80% by weight or more, or does not include crosslinked resin particles containing 90% by weight or more. The crosslinked resin particles in one embodiment of the present invention may not include PHA, in other words, one embodiment of the present invention may be configured such that the crosslinked resin particles containing PHA are not included.

[0098] <Gel fraction> In this specification, the term "crosslinked resin particles" refers to a resin particle having a crosslinked structure in which molecular chains of the resin constituting the resin particle are bonded intramolecularly and / or intermolecularly. That is, the present crosslinked resin particles may have a crosslinked structure in which molecular chains of the biodegradable resin (A) are bonded together. The amount of crosslinked structures in the crosslinked resin particles affects the gel fraction of the crosslinked resin particles, and specifically, the more crosslinked structures there are, the higher the gel fraction. The present crosslinked resin particles have a certain amount or more of crosslinked structures, and therefore exhibit a high gel fraction, specifically, a gel fraction of 50% or more. Since the present crosslinked resin particles have a gel fraction of 50% or more, the crosslinked resin particles have excellent hardness, heat resistance, and solvent resistance.

[0099] The value of the gel fraction is more preferably 60% or more, more preferably 70% or more, even more preferably 75% or more, and particularly preferably 80% or more. It may also be 85% or more, or 90% or more. The upper limit of the gel fraction is not particularly limited, and may be 100% or less. From the viewpoint of production efficiency of crosslinked resin particles, the upper limit of the gel fraction is preferably 99.5% or less, more preferably 99% or less. The upper limit of the gel fraction may also be 98% or less, 97% or less, or 96% or less.

[0100] The gel fraction is a value measured as follows: (1) A dried product of crosslinked resin particles is added to chloroform so that the concentration becomes 0.7% by weight, and the obtained mixture is kept at 60°C for 30 minutes to obtain a chloroform solution; (2) After that, the chloroform solution is allowed to stand at room temperature for 3 hours, and then the chloroform solution is filtered through a membrane filter having a pore size of 0.45 μm; (3) The gel remaining on the filter is dried, and the weight of the dried gel together with the filter is measured, and the gel fraction is calculated using the following formula. Formula: gel fraction (%)={(weight of filter including dried gel−weight of filter only) / weight of dried crosslinked resin particles used in measurement}×100.

[0101] <Volume average particle size> The crosslinked resin particles have a volume average particle diameter of 0.10 μm to 10.00 μm. This configuration allows the crosslinked resin particles to be suitably used in various applications as described below. From the viewpoint of practical use, the lower limit of the volume average particle diameter is more preferably 0.15 μm or more, and even more preferably 0.20 μm or more. Moreover, from the viewpoint of productivity (production and / or crosslinking treatment of polyhydroxyalkanoate resin, etc.), the upper limit of the volume average particle diameter is more preferably 8.00 μm or less, and even more preferably 5.00 μm or less.

[0102] In this specification, the volume average particle diameter (MV) of the crosslinked resin particles is a value obtained by measuring an aqueous dispersion liquid in which the crosslinked resin particles are dispersed in an aqueous medium. More specifically, the volume average particle diameter (MV) of the crosslinked resin particles is a value calculated by the following formula (1), i.e., formula (2), when the particle diameters of the individual crosslinked resin particles contained in a group of k total crosslinked resin particles are d1, d2,...di...dk in ascending order, and the volumes of the individual crosslinked resin particles are V1, V2,...Vi...Vk (here, the volume of the crosslinked resin particles with particle diameter di is Vi).

[0103]

number

[0104] In addition, a general-purpose measuring device can be used as a device for measuring the particle size and volume of the crosslinked resin particles in the aqueous dispersion, and an example of such a device is MicrotracMT3300EXII manufactured by Nikkiso Co., Ltd. In addition, in this specification, the volume average particle size of the uncrosslinked resin particles can be measured by replacing "crosslinked resin particles" with "uncrosslinked resin particles" in the above method.

[0105] <Median diameter (D50)> The median diameter of the crosslinked resin particles is preferably 0.10 μm to 10.00 μm. This configuration allows the crosslinked resin particles to be suitably used in various applications as described below. From the viewpoint of practical use opportunities, the lower limit of the median diameter is more preferably 0.15 μm or more, and even more preferably 0.20 μm or more. Moreover, from the viewpoint of productivity (production of biodegradable resin (A) and / or crosslinking treatment, etc.), the upper limit of the median diameter is more preferably 8.00 μm or less, and even more preferably 5.00 μm or less.

[0106] The median diameter is a value obtained by measuring using a dispersion liquid in which crosslinked resin particles are dispersed in an aqueous solvent. A general-purpose measuring device can be used as the measuring device, and an example of such a device is MicrotracMT3300EXII manufactured by Nikkiso Co., Ltd. More specifically, the particle diameter at which the larger side and the smaller side are equal (50%) in the cumulative distribution of particle diameters obtained by measurement is defined as the "median diameter (D50)".

[0107] <Glass transition temperature> The crosslinked resin particles have a glass transition temperature of 0°C or lower. This configuration has the advantage that a molded article obtained by molding a resin composition containing the crosslinked resin particles and a thermoplastic resin has excellent impact strength such as tensile impact strength, Charpy impact strength, and drop strength. This configuration also has the advantage that a molded article obtained by molding a resin composition containing the crosslinked resin particles and a thermoplastic resin has excellent tear strength. The crosslinked resin particles have a glass transition temperature of 0°C or lower, more preferably -5°C or lower. In addition, the lower limit of the glass transition temperature is more preferably -100°C or higher, and even more preferably -90°C or higher, from the viewpoint of productivity of the resin particles.

[0108] The glass transition temperature is determined as the midpoint between the temperatures at which a baseline shift begins and ends when 2 to 3 mg of crosslinked resin particles are filled into an aluminum pan, heated in a differential scanning calorimeter from -80°C to 180°C at a rate of 10°C / min under a nitrogen stream to completely melt the resin, cooled from 180°C to -80°C at a rate of 10°C / min, and then heated again from -80°C to 180°C at a rate of 10°C / min.

[0109] The method for obtaining the present crosslinked resin particles having a glass transition temperature of 0°C or lower is not particularly limited, but examples thereof include a method of using a resin having a glass transition temperature of 0°C or lower as the biodegradable resin (A) (e.g., a polyhydroxyalkanoate-based resin), a method of mixing another resin having a glass transition temperature of 0°C or lower with the biodegradable resin (A) (e.g., a polyhydroxyalkanoate-based resin) to form particles and then crosslinking the particles, a method of impregnating the obtained crosslinked resin particles with a plasticizer, and a method of crosslinking resin particles impregnated with a plasticizer.

[0110] <Peroxide> The crosslinked structure in the present crosslinked resin particles is not particularly limited, but is preferably crosslinked using a peroxide. That is, the present crosslinked resin particles are preferably crosslinked using a peroxide. When a peroxide is used, radicals generated by decomposition of the peroxide act on the molecules of the resin (e.g., biodegradable resin (A) and PHA, etc.) constituting the resin particles. This allows the molecular chains of the resin constituting the resin particles to be directly bonded to each other, forming a crosslinked structure.

[0111] When the crosslinked resin particles are crosslinked using a peroxide, the aqueous dispersion containing the crosslinked resin particles may contain a substance derived from the peroxide used to introduce the crosslinked structure (such as a decomposition product of the peroxide and unreacted peroxide). Alternatively, when the crosslinked resin particles are crosslinked using a peroxide, a substance derived from the peroxide used to introduce the crosslinked structure (such as a decomposition product of the peroxide and unreacted peroxide) may be attached to the surface of the obtained crosslinked resin particles. That is, when the crosslinked resin particles are crosslinked using a peroxide, the crosslinked resin particles may contain a substance derived from the peroxide (such as a decomposition product of the peroxide and unreacted peroxide). When the crosslinked resin particles contain a substance derived from the peroxide, it is found that the crosslinked resin particles are crosslinked using a peroxide by analyzing the crosslinked resin particles.

[0112] The peroxide may be an organic peroxide or an inorganic peroxide. The peroxide is preferably an organic peroxide because it can increase the gel fraction more efficiently.

[0113] As the organic peroxide, it is preferable to use at least one selected from the group consisting of diacyl peroxides, alkyl peroxy esters, dialkyl peroxides, hydroperoxides, peroxy ketals, peroxy carbonates, and peroxy dicarbonates, taking into consideration the heating temperature and / or time during the crosslinking treatment.

[0114] Specific examples of such organic peroxides include butyl peroxy neododecanoate, octanoyl peroxide, dilauroyl peroxide, succinic peroxide, a mixture of toluoyl peroxide and benzoyl peroxide, benzoyl peroxide, bis(butylperoxy)trimethylcyclohexane, butylperoxylaurate, dimethyldi(benzoylperoxy)hexane, bis(butylperoxy)methylcyclohexane, bis(butylperoxy)cyclohexane, and butylperoxybenzo. ester, butyl bis(butylperoxy)valerate, dicumyl peroxide, di-t-hexyl peroxide, t-butylperoxy 2-ethylhexanoate, t-butylperoxyisobutyrate, t-butylperoxypivalate, t-hexylperoxypivalate, t-butylperoxymethyl monocarbonate, t-pentylperoxymethyl monocarbonate, t-hexylperoxymethyl monocarbonate, t-heptylperoxymethyl monocarbonate, t-octylperoxymethyl monocarbonate, 1 ,1,3,3-tetramethylbutylperoxymethyl monocarbonate, t-butylperoxyethyl monocarbonate, t-pentylperoxyethyl monocarbonate, t-hexylperoxyethyl monocarbonate, t-heptylperoxyethyl monocarbonate, t-octylperoxyethyl monocarbonate, 1,1,3,3-tetramethylbutylperoxyethyl monocarbonate, t-butylperoxy n-propyl monocarbonate, t-pentylperoxy n-propyl monocarbonate, t-hexylperoxyethyl monocarbonate peroxy n-propyl monocarbonate, t-heptyl peroxy n-propyl monocarbonate, t-octyl peroxy n-propyl monocarbonate, 1,1,3,3-tetramethylbutyl peroxy n-propyl monocarbonate, t-butyl peroxy isopropyl monocarbonate, t-pentyl peroxy isopropyl monocarbonate, t-hexyl peroxy isopropyl monocarbonate, t-heptyl peroxy isopropyl monocarbonate, t-octyl peroxy isopropyl monocarbonate, 1,1,3,3-Tetramethylbutylperoxyisopropyl monocarbonate, t-butylperoxyn-butyl monocarbonate, t-pentylperoxyn-butyl monocarbonate, t-hexylperoxyn-butyl monocarbonate, t-heptylperoxyn-butyl monocarbonate, t-octylperoxyn-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxyn-butyl monocarbonate, t-butylperoxyisobutyl monocarbonate, t-pentylperoxyisobutyl monocarbonate, t -Hexylperoxyisobutylmonocarbonate, t-heptylperoxyisobutylmonocarbonate, t-octylperoxyisobutylmonocarbonate, 1,1,3,3-tetramethylbutylperoxyisobutylmonocarbonate, t-butylperoxysec-butylmonocarbonate, t-pentylperoxysec-butylmonocarbonate, t-hexylperoxysec-butylmonocarbonate, t-heptylperoxysec-butylmonocarbonate, t-octylperoxysec-butylmonocarbonate peroxy t-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy sec-butyl monocarbonate, t-butylperoxy t-butyl monocarbonate, t-pentylperoxy t-butyl monocarbonate, t-hexylperoxy t-butyl monocarbonate, t-heptylperoxy t-butyl monocarbonate, t-octylperoxy t-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy t-butyl monocarbonate, t-butylperoxy 2-ethylhexyl monocarbonate, t-pentylperoxy 2-ethylhexyl monocarbonate, ethylhexyl monocarbonate, t-hexylperoxy 2-ethylhexyl monocarbonate, t-heptylperoxy 2-ethylhexyl monocarbonate, t-octylperoxy 2-ethylhexyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy 2-ethylhexyl monocarbonate, diisobutyl peroxide, cumylperoxy neodecanoate, di-n-propylperoxydicarbonate, diisopropylperoxydicarbonate, di-sec-butylperoxydicarbonate, 1,1,3,3-Tetramethylbutylperoxyneodecanoate, bis(4-t-butylcyclohexyl)peroxydicarbonate, bis(2-ethylhexyl)peroxydicarbonate, t-hexylperoxyneodecanoate, t-butylperoxyneodecanoate, t-butylperoxyneoheptanoate, t-hexylperoxypivalate, t-butylperoxypivalate, di(3,5,5-trimethylhexanoyl)peroxide, dilauroyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, disuccinic acid peroxide, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy) Examples of organic peroxides include hexane, t-hexylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoylperoxide, t-butylperoxy-2-ethylhexylcarbonate, t-butylperoxyisopropylcarbonate, 1,6-bis(t-butylperoxycarbonyloxy)hexane, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxyacetate, t-butylperoxybenzoate, t-amylperoxy, 3,5,5-trimethylhexanoate, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, and 2,2-di-t-butylperoxybutane. The organic peroxides may be used alone or in combination of two or more.

[0115] Among these, t-butylperoxyisopropyl monocarbonate, t-pentylperoxyisopropyl monocarbonate, t-hexylperoxyisopropyl monocarbonate, t-butylperoxy2-ethylhexyl monocarbonate, t-pentylperoxy2-ethylhexyl monocarbonate, t-hexylperoxy2-ethylhexyl monocarbonate, t-amylperoxyisopropyl monocarbonate, di-t-hexyl peroxide, t-butylperoxy2-ethylhexanoate, Preferred organic peroxides are t-butyl peroxyisobutyrate, t-hexylperoxy 2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy 2-ethylhexanoate, t-butyl peroxypivalate, t-hexyl peroxypivalate, t-butyl peroxyneodecanoate, t-hexyl peroxyneodecanoate, and 1,1,3,3-tetramethylbutylperoxyneodecanoate, because they can efficiently promote crosslinking of the resin that constitutes the resin particles.

[0116] Since the heating temperature during crosslinking treatment can be set low, the peroxide is preferably a compound exhibiting a one-hour half-life temperature of 200° C. or less, more preferably a compound exhibiting a one-hour half-life temperature of 170° C. or less, and even more preferably a compound exhibiting a one-hour half-life temperature of 140° C. or less. The lower limit of the one-hour half-life temperature of the peroxide may be 50° C. or more, 60° C. or more, or 70° C. or more.

[0117] Particularly preferred organic peroxides exhibiting such a one-hour half-life temperature are t-butylperoxyisopropylmonocarbonate, t-butylperoxy2-ethylhexylmonocarbonate, di-sec-butylperoxydicarbonate, t-butylperoxy2-ethylhexanoate, t-butylperoxyisobutyrate, t-hexylperoxy2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy2-ethylhexanoate, t-butylperoxypivalate, t-hexylperoxypivalate, t-butylperoxyneodecanoate, t-hexylperoxyneodecanoate, and 1,1,3,3-tetramethylbutylperoxyneodecanoate.

[0118] The case where the peroxide is an inorganic peroxide will be described. Examples of the inorganic peroxide include hydrogen peroxide, potassium peroxide, calcium peroxide, sodium peroxide, magnesium peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate, taking into consideration the heating temperature and / or time during crosslinking treatment. Among them, hydrogen peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate are preferred in terms of ease of handling and having a decomposition temperature suitable for the heating temperature during crosslinking treatment. The inorganic peroxide may be used alone or in combination of two or more. An organic peroxide and an inorganic peroxide may be used in combination.

[0119] <Polyfunctional compounds> The crosslinked structure in the present crosslinked resin particle may be introduced by using only peroxide, but it is preferable that it is introduced by using both peroxide and polyfunctional compound.That is, it is preferable that the present crosslinked resin particle is crosslinked in the presence of peroxide and polyfunctional compound.When using both peroxide and polyfunctional compound, it is possible to increase the gel fraction of the crosslinked resin particle with a smaller amount of peroxide compared to using only peroxide.

[0120] The polyfunctional compound refers to a compound having two or more functional groups (e.g., radical reactive groups) in one molecule that can crosslink the resins (e.g., biodegradable resin (A) and PHA, etc.) that constitute the resin particles. The polyfunctional compound is not particularly limited, but is preferably a compound that is reactive with radicals generated from a peroxide, and is particularly preferably a compound having two or more radical reactive groups in one molecule. The radical reactive group is preferably at least one selected from the group consisting of a vinyl group, an allyl group, an acryloyl group, and a methacryloyl group.

[0121] Such polyfunctional compounds are not particularly limited, but examples thereof include allyl (meth)acrylate, allyl alkyl (meth)acrylates, allyloxy alkyl (meth)acrylates, polyfunctional (meth)acrylates having two or more (meth)acrylic groups, such as ethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol (meth)acrylate, divinylbenzene, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, and divinylbenzene. Preferably, the compound is one or more selected from the group consisting of allyl methacrylate, triallyl isocyanurate, butanediol di(meth)acrylate, and divinylbenzene, and more preferably, the compound is one or more selected from the group consisting of allyl methacrylate and triallyl isocyanurate.

[0122] When a crosslinked structure is formed in the presence of a polyfunctional compound, the resulting crosslinked resin particles may usually contain a structure derived from the polyfunctional compound, in which case the molecular chains of the resin constituting the resin particles are bonded to each other via the structure derived from the polyfunctional compound.

[0123] <Other ingredients, etc.> The present crosslinked resin particles are crosslinked resin particles containing a biodegradable resin (A). Therefore, the present crosslinked resin particles may be crosslinked resin particles containing only the biodegradable resin (A) having a crosslinked structure, or may be crosslinked resin particles containing other components other than the biodegradable resin (A) having a crosslinked structure. Examples of the other components include resins other than the biodegradable resin, antioxidants, hydrolysis inhibitors, antiblocking agents, crystal nucleating agents, lubricants, and ultraviolet absorbers.

[0124] The present crosslinked resin particles are different from the expanded resin particles disclosed in WO 2007 / 049694 and WO 2019 / 146555, and are preferably not expanded. In other words, the present crosslinked resin particles are preferably substantially free of air bubbles inside the particles. "Substantially free of air bubbles inside the particles" means that the volume of air bubbles (spaces) is 10% or less of the volume of the crosslinked resin particles (100%).

[0125] When the crosslinked resin particles are not expanded, the apparent density of the crosslinked resin particles is relatively large. The apparent density of the crosslinked resin particles is 0.6 g / cm. 3 It is preferable that the density exceeds 0.7 g / cm 3 More preferably, it is 0.9 g / cm or more. 3 The apparent density of the crosslinked resin particles can be determined by the method described in JIS K0061 (Method for measuring density and specific gravity of chemical products) or JIS Z8807 (Method for measuring density and specific gravity of solids).

[0126] The average weight per particle of the present crosslinked resin particles is not particularly limited. For example, when the volume average particle size or median size of the crosslinked resin particles is 10.00 μm or less, the average weight per particle of the crosslinked resin particles can be much less than 0.1 mg.

[0127] The crosslinked resin particles may be dried. The shape of the dried particles may be powder, pellets, crumbs, a film, a sheet, or the like, depending on the drying method.

[0128] <Aqueous dispersion> In one embodiment of the present invention, an aqueous dispersion is provided in which the crosslinked resin particles are dispersed in an aqueous medium.

[0129] The aqueous medium contained in the aqueous dispersion may be water alone or may be a mixed solvent of water and a water-compatible organic solvent. In the mixed solvent, the concentration of the water-compatible organic solvent is not particularly limited as long as it is equal to or lower than the solubility in water of the organic solvent used.

[0130] The organic solvent is not particularly limited, but examples thereof include alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, pentanol, hexanol, and heptanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran and dioxane; nitriles such as acetonitrile and propionitrile; amides such as dimethylformamide and acetamide; dimethyl sulfoxide; pyridine; piperidine; and the like. Among them, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, acetone, methyl ethyl ketone, tetrahydrofuran, dioxane, acetonitrile, propionitrile, and the like are preferred because they are easily removed. Moreover, methanol, ethanol, 1-propanol, 2-propanol, butanol, acetone, and the like are more preferred because they are easily available. Furthermore, methanol, ethanol, and acetone are particularly preferred.

[0131] The water content in the entire aqueous medium (100% by weight) constituting the aqueous dispersion is preferably 5% by weight to 100% by weight. The water content in 100% by weight of the aqueous medium is more preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, and particularly preferably 70% by weight or more. The water content in 100% by weight of the aqueous medium may be 90% by weight or more, or may be 95% by weight or more.

[0132] The concentration of the crosslinked resin particles in the aqueous dispersion is not particularly limited, and may be, for example, 1% by weight to 60% by weight. The aqueous dispersion may contain a dispersant, which will be described later.

[0133] <Method of Manufacturing Crosslinked Resin Particles> An example of a method for producing the present crosslinked resin particles will be specifically described. The present crosslinked resin particles can be produced by crosslinking the molecular chains of the resin in an aqueous dispersion containing resin particles before crosslinking treatment in the presence of a peroxide. The term "resin particles" refers to particles composed of a resin component that essentially constitutes the crosslinked resin particles. When the resin component is composed only of PHA, the resin particles can also be called PHA particles. In order to efficiently crosslink the molecular chains of the resin, it is preferable to heat the aqueous dispersion of the resin particles containing a peroxide to a temperature suitable for decomposing the peroxide.

[0134] More specifically, the method for producing crosslinked resin particles preferably includes the steps of: (1) preparing an aqueous dispersion of resin particles in which pre-crosslinked resin particles (e.g., PHA particles) are dispersed in water; (2) adding a peroxide to the aqueous dispersion of resin particles to impregnate the resin particles with the peroxide; and (3) heating the aqueous dispersion of resin particles impregnated with the peroxide to a heating temperature to crosslink the resin molecular chains (e.g., PHA molecular chains). More preferably, the method further includes the step of maintaining the heating temperature after all the peroxide has been added.

[0135] In step (1), for example, the aqueous dispersion of PHA particles may be an aqueous dispersion obtained by culturing a PHA-producing microorganism to accumulate PHA in the cells, and then disrupting the cells in the culture medium to separate and remove the cell components, or an aqueous dispersion obtained by concentrating or diluting the aqueous dispersion. According to such a method, the process from producing PHA particles by culturing a PHA-producing microorganism to crosslinking treatment can be carried out without separating the PHA particles from water.

[0136] Alternatively, an aqueous dispersion of resin particles (eg, PHA particles) can be prepared by dispersing dried resin particles (eg, PHA particles) in water.

[0137] The aqueous medium contained in the aqueous dispersion may be water alone or may be a mixed solvent of water and a water-compatible organic solvent. In the mixed solvent, the concentration of the water-compatible organic solvent is not particularly limited as long as it is equal to or lower than the solubility in water of the organic solvent used.

[0138] The organic solvent is not particularly limited, but examples thereof include alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, pentanol, hexanol, and heptanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran and dioxane; nitriles such as acetonitrile and propionitrile; amides such as dimethylformamide and acetamide; dimethyl sulfoxide; pyridine; piperidine; and the like. Among them, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, acetone, methyl ethyl ketone, tetrahydrofuran, dioxane, acetonitrile, propionitrile, and the like are preferred because they are easily removed. Moreover, methanol, ethanol, 1-propanol, 2-propanol, butanol, acetone, and the like are more preferred because they are easily available. Furthermore, methanol, ethanol, and acetone are particularly preferred.

[0139] The water content in the entire aqueous medium (100% by weight) constituting the aqueous dispersion is preferably 5% by weight to 100% by weight. The water content in 100% by weight of the aqueous medium is more preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, and particularly preferably 70% by weight or more. The water content in 100% by weight of the aqueous medium may be 90% by weight or more, or may be 95% by weight or more.

[0140] In the aqueous dispersion, the volume average particle size and median size of the resin particles are preferably within the same range as the volume average particle size and median size of the crosslinked resin particles described above, respectively. When PHA resin particles produced by PHA-producing microorganisms are used as a raw material, the volume average particle size of the PHA resin particles can usually be within the above range. Therefore, when resin particles produced by PHA-producing microorganisms are used as a raw material, an aqueous dispersion of resin particles having a desired volume average particle size can be obtained without carrying out a special process for adjusting the particle size. When PHA resin particles produced by PHA-producing microorganisms are used as a raw material, the median size of the PHA resin particles can usually be within the above range. Therefore, when resin particles produced by PHA-producing microorganisms are used as a raw material, an aqueous dispersion of resin particles having a desired median size can be obtained without carrying out a special process for adjusting the particle size.

[0141] The concentration of the resin particles in the aqueous dispersion is not particularly limited and can be set appropriately, but may be, for example, about 1 to 70% by weight, and preferably about 5 to 50% by weight.

[0142] The aqueous dispersion of resin particles preferably contains a dispersant in order to increase the dispersibility of the resin particles and to uniformly proceed with the crosslinking reaction. Examples of dispersants include anionic surfactants such as dioctyl sodium sulfosuccinate, sodium dodecyl sulfate, sodium lauryl sulfate, and sodium oleate; cationic surfactants such as lauryl trimethyl ammonium chloride; nonionic surfactants such as glycerin fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, and polyoxyethylene polyoxypropylene glycol; and water-soluble polymers such as polyvinyl alcohol, ethylene-modified polyvinyl alcohol, polyvinylpyrrolidone, methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, polyacrylic acid, sodium polyacrylate, potassium polyacrylate, polymethacrylic acid, and sodium polymethacrylate. Only one of these dispersants may be used, or two or more of them may be used in combination.

[0143] When a dispersant is used, the content (addition amount) of the dispersant in the aqueous dispersion is not particularly limited. The content of the dispersant in the aqueous dispersion may be, for example, 0.1 to 10 parts by weight, preferably 0.5 to 5 parts by weight, and particularly preferably 0.5 to 3 parts by weight, based on 100 parts by weight of the resin particles.

[0144] In step (2), a peroxide is added to the aqueous dispersion of resin particles obtained in step (1) to impregnate the resin particles with the peroxide. The peroxide may be any of those mentioned above. Peroxide may be added in various forms, such as solid or liquid. Alternatively, a liquid form diluted with a diluent may be added. The peroxide may be added all at once, or may be added continuously or in portions.

[0145] When the peroxide and the polyfunctional compound are used in combination, it is preferable to add the polyfunctional compound to the aqueous dispersion of the resin particles in step (2). The polyfunctional compound can be any of those mentioned above. The polyfunctional compound can be added in various forms, such as solid or liquid. A liquid diluted with a diluent or the like may also be added. The polyfunctional compound may be added all at once, continuously, or in portions.

[0146] In step (2), the method of impregnating the resin particles with the peroxide and any polyfunctional compound may be such that, after or while adding these compounds to the aqueous dispersion of the resin particles, the temperature of the aqueous dispersion is set to, for example, 0°C or higher but lower than a temperature suitable for decomposing the peroxide employed in the next step (3), and the temperature is maintained, for example, for about 1 minute to 5 hours while stirring the aqueous dispersion. Specifically, the temperature of the aqueous dispersion during impregnation may be about 10°C to 60°C.

[0147] The amount of the peroxide used can be appropriately set in consideration of the gel fraction of the crosslinked resin particles. For example, the amount of the peroxide used is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 8 parts by weight, further preferably 0.3 to 5 parts by weight, and particularly preferably 0.5 to 3 parts by weight, relative to 100 parts by weight of the resin particles.

[0148] According to a manufacturing method in which resin particles are crosslinked in an aqueous dispersion using a peroxide, crosslinking can be promoted while maintaining the particle size (volume) before crosslinking, and crosslinked resin particles can be easily obtained. On the other hand, in a method in which a resin is crosslinked by melt kneading in the presence of a peroxide, this can be difficult to achieve.

[0149] In addition, the manufacturing method in which resin particles are crosslinked in an aqueous dispersion using a peroxide has the advantage that it is easy to control the temperature increase caused by the heat generated during the crosslinking reaction, and crosslinked resin particles having a safe and stable crosslinked structure (quality) can be efficiently obtained.

[0150] The amount of the polyfunctional compound used may be appropriately set in consideration of the gel fraction of the crosslinked resin particles. The amount of the polyfunctional compound used is, for example, preferably 0.01 to 20 parts by weight, more preferably 0.05 to 15 parts by weight, even more preferably 0.1 to 10 parts by weight, even more preferably 0.2 to 5 parts by weight, and particularly preferably 0.3 to 3 parts by weight, relative to 100 parts by weight of the resin particles.

[0151] In step (3), the aqueous dispersion of resin particles impregnated with the peroxide is heated to a temperature suitable for decomposing the peroxide. The heating temperature is preferably within a range of about 25°C above and below the one-hour half-life temperature of the peroxide (one-hour half-life temperature -25°C to one-hour half-life temperature +25°C). Specifically, the heating temperature is preferably 30°C to 140°C, more preferably 50°C to 135°C, and even more preferably 60°C to 130°C. According to this method, it is possible to crosslink the resin at a temperature lower than the melting temperature of the resin (e.g., PHA), so that deterioration of the resin due to heating during the crosslinking treatment can be avoided. The melting temperature of PHA is, for example, 50°C to 210°C.

[0152] In the subsequent step (4), it is preferable to maintain the heating temperature. This allows the crosslinking reaction using the peroxide to proceed sufficiently. The time for maintaining the heating temperature is not particularly limited, but is preferably 1 minute to 15 hours, and more preferably 1 hour to 10 hours.

[0153] After the crosslinking reaction is completed, the crosslinked resin particles are separated from the aqueous dispersion, and water is removed from the separated crosslinked resin particles to obtain dried crosslinked resin particles. The method for separating the crosslinked resin particles from the aqueous dispersion is not particularly limited, and for example, filtration, centrifugation, heat drying, freeze drying, spray drying, etc. can be used. For example, spray drying can be used to obtain dried crosslinked resin particles directly from the aqueous dispersion. In addition, by extruding the crosslinked resin particles alone after separation from the aqueous dispersion, the crosslinked resin particles can be obtained in the form of pellets while completely removing the remaining moisture. In addition, an aggregation process using a coagulant and / or adjusting the pH may be performed.

[0154] The aqueous dispersion itself after the crosslinking reaction, the aqueous dispersion obtained by concentrating the aqueous dispersion after the crosslinking reaction to increase the concentration of the crosslinked resin particles, or the aqueous dispersion obtained by diluting the aqueous dispersion after the crosslinking reaction by adding an aqueous medium also constitute one aspect of the present invention. In addition, (i) an aqueous dispersion with an adjusted pH, and / or (ii) an aqueous dispersion to which other additives such as a dispersant, an antioxidant, a hydrolysis inhibitor, an antiblocking agent, a crystal nucleating agent, or an ultraviolet absorber have been added also constitute one aspect of the present invention.

[0155] <Applications of crosslinked resin particles> The crosslinked resin particles according to one embodiment of the present invention are not particularly limited in use, and can be used in applications where conventionally known crosslinked resin particles are used.Specific examples include resin modifiers, rheology adjusters for paints or adhesives, paint pigments, paper coating agents, matting agents, antiblocking agents, cosmetic additives, toner additives, liquid crystal spacers, coating agents, fillers for adhesive tapes, fiber processing agents, medical diagnostic test particles, fillers, aqueous coating films, coated paper, resin tubes, foamed particles, packaging materials, containers, cosmetic containers, antifouling resin compositions, heat seal paper, handle moldings, forks, films, resin films for twist packaging materials, bags, gloves, binding materials, multilayer films, stretched films, fibers, multifilaments, meltblown nonwoven fabrics, masks, pile fabrics, coffee filters, inflation moldings, blow moldings, calendar sheet moldings, injection moldings, laminates, films, sheets, etc.The uses of the crosslinked resin particles are not limited to these.

[0156] [2. Resin composition] A thermoplastic resin composition according to one embodiment of the present invention contains a thermoplastic resin and the crosslinked resin particles described above in the section [1. Crosslinked resin particles].

[0157] In this specification, "the thermoplastic resin composition according to one embodiment of the present invention" may be referred to as "the present resin composition".

[0158] Since the resin composition has the above-mentioned structure, it can fully enjoy the effect of improving mechanical strength such as impact strength by the crosslinked resin particles, and as a result, the molded article of the thermoplastic resin composition has the advantage of being excellent in impact resistance.

[0159] A molded article can be obtained by molding the thermoplastic resin composition by a known method.

[0160] The content of the crosslinked resin particles in the resin composition is not particularly limited. The content of the crosslinked resin particles in the resin composition may be 0.1 parts by weight or more, 0.3 parts by weight or more, 0.5 parts by weight or more, 1 part by weight or more, 5 parts by weight or more, 7 parts by weight or more, 10 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, or 30 parts by weight or more, based on 100 parts by weight of the total of the thermoplastic resin and the crosslinked resin particles. The content of the crosslinked resin particles in the resin composition is preferably 60 parts by weight or less, more preferably 55 parts by weight or less, even more preferably 53 parts by weight or less, and particularly preferably 50 parts by weight or less, based on 100 parts by weight of the total of the thermoplastic resin and the crosslinked resin particles. The content of the crosslinked resin particles in the present resin composition may be 45 parts by weight or less, 40 parts by weight or less, 30 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, 12 parts by weight or less, or 10 parts by weight or less, based on 100 parts by weight of the total of the thermoplastic resin and the crosslinked resin particles.

[0161] <Thermoplastic resin> In the present resin composition, the thermoplastic resin can be said to be a matrix resin. The thermoplastic resin is not particularly limited as long as it is a resin that can be molded into a desired shape by melting it by heating and then cooling and solidifying it. Specific examples of the thermoplastic resin include polyolefin resins such as polyethylene and polypropylene, acrylic resins such as polyvinyl chloride, polystyrene, polyvinyl acetate, polyurethane, polytetrafluoroethylene, and polymethyl methacrylic acid, AS resins, polyamides, polyacetals, polycarbonates, modified polyphenylene ethers, polyester resins, and cyclic polyolefins. These thermoplastic resins may be used alone or in combination of two or more. The thermoplastic resin preferably has a gel fraction of less than 50%. The thermoplastic resin is preferably not crosslinked.

[0162] As the thermoplastic resin, polyester-based resins are particularly preferred, such as aliphatic polyesters (e.g., PHA, PLA, PCL, and aliphatic polyesters having a structure in which an aliphatic diol and an aliphatic dicarboxylic acid are polycondensed, etc.) and aliphatic aromatic polyesters.

[0163] The specific aspects of the aliphatic polyester and the aliphatic aromatic polyester are the same as those described in the section <Biodegradable resin (A)> of [1. Crosslinked resin particles] above, so the description is incorporated herein by reference and will not be repeated here.

[0164] Since the crosslinked resin particles contain a biodegradable resin (A) having biodegradability, it is preferable that the thermoplastic resin also contains a resin having biodegradability, i.e., a biodegradable resin. For convenience, the biodegradable resin contained in the thermoplastic resin may be referred to as "biodegradable resin (B)". In other words, it is preferable that the thermoplastic resin contains a biodegradable resin (B). This configuration has the advantage that the biodegradability of the entire thermoplastic resin composition and the entire molded product of the thermoplastic resin composition can be increased.

[0165] The biodegradable resin (B) contained in the thermoplastic resin may be a biodegradable resin having a glass transition temperature of 0°C or lower, a biodegradable resin having a glass transition temperature of more than 0°C, or a mixture of a biodegradable resin having a glass transition temperature of 0°C or lower and a biodegradable resin having a glass transition temperature of more than 0°C. Since the effects of blending crosslinked resin particles (for example, the effect of improving impact resistance) can be enjoyed more, it is preferable that the biodegradable resin (B) contained in the thermoplastic resin contains a biodegradable resin having a glass transition temperature of 0°C or higher in an amount of preferably 50% by weight or more, more preferably 60% by weight or more, even more preferably 70% by weight or more, and particularly preferably 80% by weight or more of a biodegradable resin having a glass transition temperature of 0°C or higher, based on 100% by weight of the biodegradable resin (B). The biodegradable resin (B) may be composed only of a biodegradable resin having a glass transition temperature of 0°C or higher.

[0166] Furthermore, when the crosslinked resin particles contain a resin produced from a plant-derived raw material, from the viewpoint of resource circulation, it is preferable that the thermoplastic resin also contains a resin produced from a plant-derived raw material, and it is more preferable that the thermoplastic resin is composed only of a resin produced from a plant-derived raw material.

[0167] The case where the thermoplastic resin contains a biodegradable resin (B) will be described. The thermoplastic resin preferably contains 10% by weight to 100% by weight of the biodegradable resin (B) in 100% by weight of the thermoplastic resin. The thermoplastic resin more preferably contains 30% by weight or more of the biodegradable resin (B) in 100% by weight of the thermoplastic resin, more preferably contains 50% by weight or more, even more preferably contains 70% by weight or more, and particularly preferably contains 90% by weight or more. The thermoplastic resin may be composed only of the biodegradable resin (B).

[0168] Since the thermoplastic resin composition and its molded article can enjoy the impact resistance improving effect of the crosslinked resin particles, the biodegradable resin (B) preferably contains a polyester resin, more preferably contains an aliphatic polyester, and particularly preferably contains PHA and / or polylactic acid. The PHA used as the thermoplastic resin preferably has a gel fraction of less than 50%. The PHA used as the thermoplastic resin preferably does not have a crosslinked structure.

[0169] The case where the thermoplastic resin contains PHA and / or polylactic acid as the biodegradable resin (B) will be described below. The thermoplastic resin preferably contains 10% by weight to 100% by weight of PHA and polylactic acid in total, more preferably 30% by weight or more, even more preferably 50% by weight or more, even more preferably 70% by weight or more, and particularly preferably 90% by weight or more, based on 100% by weight of the thermoplastic resin.

[0170] The PHA that can be used as the thermoplastic resin is not particularly limited, and examples thereof include polyglycolic acid, P3HA, poly(4-hydroxyalkanoate) resins, etc. As the PHA, only one type may be used, or two or more types may be used in combination. As the PHA used as the thermoplastic resin, P3HA is particularly preferred.

[0171] A case where the crosslinked resin particles contain P3HA and the thermoplastic resin contains P3HA will be described. The P3HA that can be used as the thermoplastic resin is the same as the P3HA related to the crosslinked resin particles, and the various P3HAs described above can be used. The P3HA contained in the thermoplastic resin may be a resin with the same composition as the P3HA contained in the crosslinked resin particles, or may be a resin with a different composition and / or physical properties. The P3HA contained in the thermoplastic resin is preferably a resin with a different composition and / or physical properties from the P3HA contained in the crosslinked resin particles, and more preferably a resin that is harder than the P3HA contained in the crosslinked resin particles.

[0172] The case where the P3HA used as the thermoplastic resin contains 3-hydroxybutanoic acid (3HB) repeating units will be described. In this case, from the viewpoint of the balance between flexibility and strength, the composition ratio of the 3HB repeating units in the total monomer repeating units of P3HA (100 mol%) is preferably 80 mol% to 99 mol%, and more preferably 82 mol% to 97 mol%. When the composition ratio of the 3HB repeating units in P3HA is 80 mol% or more, the rigidity of P3HA can be improved. On the other hand, when the composition ratio of the 3HB repeating units in P3HA is 99 mol% or less, the flexibility of P3HA tends to be improved. As P3HA, two or more types having different composition ratios of the 3HB repeating units may be used in combination.

[0173] The weight average molecular weight of the PHA used as the thermoplastic resin is not particularly limited, but is preferably 50,000 to 3,000,000, more preferably 100,000 to 2,000,000, and even more preferably 150,000 to 1,500,000. When the weight average molecular weight of the PHA is 50,000 or more, sufficient rigidity and / or strength can be obtained in the present resin composition and its molded article. On the other hand, a PHA having a weight average molecular weight of 3,000,000 or less may have the advantage that the PHA is easy to manufacture and / or easy to handle in order to achieve the object of one embodiment of the present invention.

[0174] Regarding the PHA and polylactic acid used as the thermoplastic resin, other aspects than those described above are the same as those explained in the section <Biodegradable resin (A)> above, so the explanation therefor is incorporated by reference and will not be repeated here.

[0175] The content of the thermoplastic resin in the resin composition is not particularly limited. The content of the thermoplastic resin in the resin composition is preferably 40 parts by weight to 99.9 parts by weight, more preferably 40 parts by weight to 99.7 parts by weight, more preferably 40 parts by weight to 99.5 parts by weight, more preferably 40 parts by weight to 99 parts by weight, and even more preferably 40 parts by weight to 95 parts by weight, in the total of 100 parts by weight of the thermoplastic resin and the crosslinked resin particles. According to this configuration, the thermoplastic resin composition can provide a molded product having excellent impact resistance. The content of the thermoplastic resin in the resin composition may be 45 parts by weight to 93 parts by weight, 47 parts by weight to 90 parts by weight, 50 parts by weight to 80 parts by weight, 50 parts by weight to 75 parts by weight, or 50 parts by weight to 70 parts by weight, in the total of 100 parts by weight of the thermoplastic resin and the crosslinked resin particles. The content of the thermoplastic resin in the present resin composition may be 55 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 85 parts by weight or more, 88 parts by weight or more, or 90 parts by weight or more, based on 100 parts by weight of the total of the thermoplastic resin and the crosslinked resin particles.

[0176] <Nucleating agent> The present resin composition may further contain a crystal nucleating agent. When the thermoplastic resin composition contains a crystal nucleating agent, crystallization during molding is promoted in the case where the thermoplastic resin is a crystalline resin, and molding processability, productivity, etc. can be improved. When the present resin composition contains a crystal nucleating agent, it also has the advantage that a thermoplastic resin composition and a molded article thereof having excellent heat resistance or mechanical properties can be obtained.

[0177] The crystal nucleating agent is not particularly limited, and conventionally known ones can be used. The crystal nucleating agent can be, for example, inorganic substances such as talc, kaolinite, montmorillonite, mica, synthetic mica, clay, zeolite, silica, carbon black, graphite, boron nitride, zinc oxide, titanium oxide, tin oxide, calcium carbonate, magnesium carbonate, aluminum oxide, neodymium oxide, barium sulfate, sodium chloride, and metal phosphate; sugar alcohol compounds derived from natural products such as erythritol, pentaerythritol, galactitol, mannitol, and arabitol; polysaccharides such as chitin and chitosan; polyols such as aliphatic alcohols (polyols), polyvinyl alcohol, and polyethylene oxide; sodium benzoate, potassium benzoate, lithium benzoate, calcium benzoate, magnesium benzoate, barium benzoate, lithium terephthalate, sodium terephthalate, and terephthalic acid salts. metal salts of organic carboxylic acids such as potassium phosphate, calcium oxalate, sodium laurate, potassium laurate, sodium myristate, potassium myristate, calcium myristate, sodium octacosanoate, calcium octacosanoate, sodium stearate, potassium stearate, lithium stearate, calcium stearate, magnesium stearate, barium stearate, sodium montanate, calcium montanate, sodium toluate, sodium salicylate, potassium salicylate, zinc salicylate, aluminum dibenzoate, potassium dibenzoate, lithium dibenzoate, sodium β-naphthalate, and sodium cyclohexanecarboxylate; organic sulfonates such as sodium p-toluenesulfonate and sodium sulfoisophthalate;Carboxylic acid amides such as ethylene stearic acid amide, ethylene bislauric acid amide, palmitic acid amide, hydroxystearic acid amide, erucic acid amide, and trimesic acid tris(t-butylamide), lauric acid esters, palmitic acid esters, oleic acid esters, stearic acid esters, erucic acid esters, N-oleyl palmitic acid ester, N-oleyl oleic acid ester, N-oleyl stearate ester, N-stearyl oleic acid ester, N-stearyl stearate ester, N-stearyl erucic acid ester, methylene bisstearate ester, ethylene bislauric acid ester, ethylene biscapric acid ester, ethylene bisoleic acid ester, ethylene bisstearic acid ester, ethylene biserucic acid ester, ethylene Examples of the nucleating agent include carboxylic acid esters such as butylene bisisostearate, butylene bisstearate, and p-xylylene bisstearate; dicarboxylic acid derivatives such as dimethyl adipate, dibutyl adipate, diisodecyl adipate, and dibutyl sebacate; cyclic compounds having a functional group C=O and one or more functional groups selected from the group consisting of NH, S, and O in the molecule, such as indigo, quinacridone, and quinacridone magenta; sorbitol derivatives such as bisbenzylidene sorbitol and bis(p-methylbenzylidene) sorbitol; compounds containing a nitrogen-containing heteroaromatic nucleus such as pyridine, triazine, and imidazole; phosphoric acid ester compounds, bisamides of higher fatty acids, and metal salts of higher fatty acids; branched polylactic acid; and low molecular weight poly(3-hydroxybutyrate). These crystal nucleating agents may be used alone or in combination of two or more.

[0178] The content of the crystal nucleating agent is not particularly limited as long as it can promote the crystallization of the thermoplastic resin. The content of the crystal nucleating agent is preferably 0.05 parts by weight to 12.00 parts by weight, more preferably 0.10 parts by weight to 10.00 parts by weight, and even more preferably 0.50 parts by weight to 8.00 parts by weight, relative to 100 parts by weight of the thermoplastic resin. When the content of the crystal nucleating agent is within the above range, the effect of the crystal nucleating agent can be obtained while suppressing the decrease in viscosity during molding and the physical properties of the molded product.

[0179] <Lubricant> The resin composition may further contain a lubricant. When the thermoplastic resin composition contains a lubricant, the surface smoothness of the obtained molded article can be improved. The lubricant is not particularly limited. Examples of the lubricant include, but are not limited to, fatty acid metal salts such as magnesium stearate and calcium stearate; fatty acid amides such as behenic acid amide, stearic acid amide, erucic acid amide, oleic acid amide, methylene bisstearic acid amide, and ethylene bisstearic acid amide; polyethylene wax, oxidized polyester wax, glycerin mono fatty acid esters such as glycerin monostearate, glycerin monobehenate, and glycerin monolaurate; organic acid monoglycerides such as succinic acid saturated fatty acid monoglycerides; sorbitan fatty acid esters such as sorbitan behenate, sorbitan stearate, and sorbitan laurate; polyglycerin fatty acid esters such as diglycerin stearate, diglycerin laurate, tetraglycerin stearate, tetraglycerin laurate, decaglycerin stearate, and decaglycerin laurate; and higher alcohol fatty acid esters such as stearyl stearate. The lubricant may be used alone or in combination of two or more.

[0180] The content of the lubricant (when a plurality of lubricants are used, the total content thereof) is not particularly limited as long as it can impart lubricity to the molded body. The content of the lubricant is preferably 0.01 to 20.00 parts by weight, more preferably 0.05 to 10.00 parts by weight, even more preferably 0.10 to 10.00 parts by weight, even more preferably 0.20 to 5.00 parts by weight, and particularly preferably 0.30 to 4.00 parts by weight, relative to 100 parts by weight of the thermoplastic resin. When the content of the lubricant is within the above range, it is possible to obtain the effect as a lubricant while avoiding the bleeding out of the lubricant onto the surface of the molded body.

[0181] <Other ingredients> The present resin composition may contain other components, such as plasticizers, organic fillers, inorganic fillers, antioxidants, hydrolysis inhibitors, ultraviolet absorbers, colorants such as dyes and pigments, and antistatic agents, to the extent that the functions of the resulting molded article are not impaired.

[0182] The plasticizer is not particularly limited. Examples of the plasticizer include polyester-based plasticizers such as polypropylene glycol sebacate ester, aliphatic dibasic acid ester-based plasticizers such as di-1-butyl adipate, di-n-butyl sebacate, and di-2-ethylhexyl azelate, glycerin-based plasticizers such as glycerin diacetomonolaurate, glycerin diacetomonocaprylate, and glycerin diacetomonodecanoate, polycarboxylic acid ester-based plasticizers such as tri-2-ethylhexyl acetyl citrate and tributyl acetyl citrate, and polyamide-based plasticizers such as polyethylene glycol, polypropylene glycol, poly(ethylene oxide-propylene oxide) block and / or random copolymers, and polytetramethylene glycol. Examples of the plasticizer include alkylene glycol-based plasticizers, phosphoric acid ester-based plasticizers such as diphenyl-2-ethylhexyl phosphate and diphenyloctyl phosphate, epoxy-based plasticizers such as epoxidized soybean oil and epoxidized linseed oil fatty acid butyl ester, and castor oil-based plasticizers such as castor oil fatty acid esters, methyl ricinoleate, ethyl ricinoleate, isopropyl ricinoleate, butyl ricinoleate, ethylene glycol monoricylate, propylene glycol monoricylate, trimethylolpropane monoricylate, sorbitan monoricylate, castor oil fatty acid polyethylene glycol ester, castor oil ethylene oxide adduct, castor oil-based polyol, castor oil-based toluol, and castor oil-based diol. These plasticizers may be used alone or in combination of two or more.

[0183] The organic filler is not particularly limited. Examples of the organic filler include fillers made of naturally derived materials such as wood-based materials (e.g., wood chips, wood flour, sawdust, etc.), rice husks, rice flour, starch, corn starch, rice straw, wheat straw, and natural rubber; organic fibers such as natural vegetable fibers, natural animal fibers, and synthetic fibers; and fillers made of synthetic resin materials such as polyester, polyacrylic, polyamide, nylon, polyethylene, polyolefin, polyvinyl alcohol, polyvinyl chloride, polyurethane, polyacetal, aramid, PBO (poly-p-phenylene benzobisoxazole), polyphenylene sulfide, acetyl cellulose, polybenzazole, polyarylate, polyvinyl acetate, and synthetic rubber.

[0184] The plant-derived natural fibers are not particularly limited. Examples of the plant-derived natural fibers include kenaf fiber, abaca fiber, bamboo fiber, jute fiber, hemp fiber, linen fiber, henequen (sisal), ramie fiber, hemp, cotton, banana fiber, coconut fiber, palm, paper mulberry, mitsumata, bagasse, etc. In addition, regenerated fibers such as pulp, cellulose fiber, and rayon processed from plant fibers are also included. Examples of the animal-derived natural fibers include wool, silk, cashmere, and mohair.

[0185] The inorganic filler is not particularly limited. Examples of the inorganic filler include silica-based inorganic fillers (e.g., quartz, fumed silica, silicic anhydride, fused silica, crystalline silica, amorphous silica, fillers obtained by condensing alkoxysilanes, ultrafine amorphous silica, etc.), alumina, zircon, iron oxide, zinc oxide, titanium oxide, silicon nitride, boron nitride, aluminum nitride, silicon carbide, glass, silicone rubber, silicone resin, titanium oxide, carbon fiber, mica, graphite, carbon black, ferrite, graphite, diatomaceous earth, white clay, clay, talc, calcium carbonate, manganese carbonate, magnesium carbonate, barium sulfate, silver powder, etc. These inorganic fillers may be surface-treated to increase dispersibility in the resin composition. In addition, these inorganic fillers may be used alone or in combination of two or more.

[0186] The antioxidant is not particularly limited. Examples of the antioxidant include phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants. These antioxidants may be used alone or in combination of two or more.

[0187] The hydrolysis inhibitor is not particularly limited. Examples of the hydrolysis inhibitor include carbodiimide compounds, epoxy compounds, isocyanate compounds, and oxazoline compounds. These hydrolysis inhibitors may be used alone or in combination of two or more.

[0188] The ultraviolet absorbing agent is not particularly limited. Examples of the ultraviolet absorbing agent include benzophenone compounds, benzotriazole compounds, triazine compounds, salicylic acid compounds, cyanoacrylate compounds, and nickel complex compounds. These ultraviolet absorbing agents may be used alone or in combination of two or more.

[0189] The coloring agent such as the pigment or dye is not particularly limited. Examples of the coloring agent include inorganic coloring agents such as titanium oxide, calcium carbonate, chromium oxide, cuprous oxide, calcium silicate, iron oxide, carbon black, graphite, titanium yellow, and cobalt blue; soluble azo pigments such as lake red, lithol red, and brilliant carmine; insoluble azo pigments such as dinitrile orange and fast yellow; phthalocyanine pigments such as monochlorophthalocyanine blue, polychlorophthalocyanine blue, and polybromophthalocyanine green; condensed polycyclic pigments such as indigo blue, perylene red, isoindolinone yellow, and quinacridone red; and dyes such as oracet yellow. These coloring agents may be used alone or in combination of two or more.

[0190] The antistatic agent is not particularly limited. Examples of the antistatic agent include low molecular weight antistatic agents such as fatty acid ester compounds, aliphatic ethanolamine compounds, and aliphatic ethanolamide compounds, and polymeric antistatic agents. These antistatic agents may be used alone or in combination of two or more.

[0191] The resin composition may further contain, as additives, catalyst deactivators (hindered phenol compounds, thioether compounds, vitamin compounds, triazole compounds, polyamine compounds, hydrazine derivative compounds, phosphorus compounds, etc.), release agents (montanic acid and its salts, its esters, its half esters, stearyl alcohol, stearamide, polyethylene wax, etc.), color inhibitors (phosphites, hypophosphites, etc.), silane coupling agents (epoxy silane coupling agents, amino silane coupling agents, (meth)acrylic silane coupling agents, isocyanate silane coupling agents, etc.), flame retardants (red phosphorus, phosphate esters, brominated polystyrene, brominated polyphenylene ether ... It may also contain: aliphatic compounds such as carboxylic acid, carboxylic acid di ...

[0192] The content of each of the other components described above is not particularly limited as long as the effect of one embodiment of the present invention is exhibited, and can be appropriately set by a person skilled in the art.

[0193] <Method of producing thermoplastic resin composition> The resin composition can be produced by a known method. Specifically, a method of melt-kneading a thermoplastic resin, crosslinked resin particles, and optional components such as a crystal nucleating agent, a lubricant, and other components using an extruder, a kneader, a Banbury mixer, a kneading roll, or the like can be mentioned. When melt-kneading, it is preferable to mix while paying attention to the decrease in molecular weight due to thermal decomposition. In addition, the thermoplastic resin composition can also be produced by dissolving all the raw materials (components) in a soluble solvent and then removing the solvent.

[0194] When producing a thermoplastic resin composition by melt kneading, each component may be individually charged into an extruder, etc., or each component may be mixed in advance and the resulting mixture may be charged into an extruder, etc. For example, an aqueous dispersion of a thermoplastic resin and an aqueous dispersion of crosslinked resin particles may be mixed, and then the resulting mixture may be dried in a dryer to obtain a mixed powder, and the mixed powder may be charged into an extruder, etc.

[0195] When melt kneading is performed using an extruder, the obtained thermoplastic resin composition may be extruded from the extruder into a strand shape and then cut, thereby processing the thermoplastic resin composition into particle shapes such as a bar shape, a cylinder shape, an elliptical cylinder shape, a sphere shape, a cube shape, a rectangular parallelepiped shape, or the like.

[0196] The resin temperature during melt kneading cannot be generally defined because it depends on the melting point and melt viscosity of the resin used, etc. The resin temperature is preferably 140°C to 250°C, more preferably 150°C to 230°C, and even more preferably 160°C to 210°C, from the viewpoint of uniformly dispersing the crosslinked resin particles in the thermoplastic resin while avoiding thermal decomposition of the thermoplastic resin.

[0197] <Method of manufacturing molded body> In one embodiment of the present invention, a molded article is provided by molding the resin composition. The molding method of the thermoplastic resin composition is not particularly limited, and a commonly used molding method can be applied. Specific examples of the molding method include inflation film molding, extrusion blow molding, injection blow molding, extrusion molding, calendar molding, vacuum molding, injection molding, and the like. The molded article formed by molding the thermoplastic resin composition can also be said to be a molded article containing the thermoplastic resin composition.

[0198] By carrying out the above-mentioned molding method using the present resin composition, a molded product having excellent impact resistance, specifically, a film molded product, a sheet molded product, a blow molded product, an extrusion molded product, a vacuum molded product, or an injection molded product, can be produced with good productivity. In this specification, the term "film molded product" refers to a product conforming to JIS20108:2012, specifically, a thin film having a thickness of less than 0.25 mm. In this specification, the term "sheet molded product" refers to a product conforming to JIS20108:2012, specifically, a thin plate having a thickness of 0.25 mm or more.

[0199] Molded articles containing the present resin composition can be suitably used in fields such as agriculture, fisheries, forestry, horticulture, medicine, sanitary products, the food industry, clothing, non-clothing, packaging, automobiles, building materials, and others.

[0200] [3. Modifiers for thermoplastic resins] One embodiment of the present invention provides a modifier for thermoplastic resins, comprising crosslinked resin particles, the crosslinked resin particles comprising a biodegradable resin (A) having a glass transition temperature of less than 0° C. and having a gel fraction of 50% or more. The modifier for thermoplastic resins according to one embodiment of the present invention can provide a resin composition capable of providing a molded article having excellent impact resistance by being blended with a thermoplastic resin.

[0201] For each aspect of the thermoplastic resin modifier, the description in the above section [1. Crosslinked resin particles] is incorporated as appropriate. EXAMPLES

[0202] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0203] [Evaluation method] The volume average particle size, median size (D50), gel fraction, and glass transition temperature of the crosslinked resin particles prepared in the examples and comparative examples, as well as the tensile impact strength of the molded articles obtained by molding the thermoplastic resin compositions, were measured by the methods described below.

[0204] (Volume average particle size) The volume average particle diameter of the crosslinked resin particles was measured using an aqueous dispersion of the crosslinked resin particles as a sample. A MicrotracMT3300EXII manufactured by Nikkiso Co., Ltd. was used as a measuring device. Specifically, the particle diameter and volume of each crosslinked resin particle in the aqueous dispersion of the crosslinked resin particles were measured using the above device, and the volume average particle diameter was calculated from the results obtained by the measurement based on the above-mentioned formula (1), i.e., formula (2).

[0205] (Median diameter (D50)) The median diameter of the crosslinked resin particles was measured using an aqueous dispersion of the crosslinked resin particles as a sample. The measuring device used was a MicrotracMT3300EXII manufactured by Nikkiso Co., Ltd. More specifically, the particle diameter at which the larger and smaller sides were equal (50%) in the cumulative distribution of particle diameters obtained by the measurement was defined as the "median diameter (D50)".

[0206] (Gel fraction) The dried crosslinked resin particles were added to chloroform to a concentration of 0.7% by weight, and the mixture was kept at 60°C for 30 minutes to obtain a chloroform solution. After that, the mixture was left to stand at room temperature for 3 hours, and then the chloroform solution was filtered through a membrane filter with a pore size of 0.45 μm. The inside of the container and the filter were thoroughly washed with chloroform several times while filtering to prevent loss. The gel remaining on the filter was dried, and the weight of the filter was measured, and the gel fraction was calculated using the following formula. Formula: Gel fraction = (weight of filter including dry gel - weight of filter only) / weight of crosslinked resin particles or uncrosslinked resin particles used in measurement x 100 (%) (Method of measuring glass transition temperature (Tg)) The temperature determined by the following method (differential scanning calorimetry (DSC)) was taken as the glass transition temperature of the resin (biodegradable resin, PHA, etc.), crosslinked resin particles, or uncrosslinked resin particles: (1) 2 mg to 3 mg of resin, crosslinked resin particles, or uncrosslinked resin particles were filled into an aluminum pan; (2) The aluminum pan was placed in a differential scanning calorimeter, and the temperature of the analyzer was raised from -80°C to 180°C at a rate of 10°C / min under a nitrogen stream to completely melt the resin; (3) The temperature of the analyzer was then lowered from 180°C to -80°C at a rate of 10°C / min; (4) The temperature of the analyzer was again raised from -80°C to 180°C at a rate of 10°C / min; (5) For the DSC curve obtained in (4) above, the intermediate temperature between the temperature at which the shift (change) from the baseline started and the temperature at which it ended was taken as the glass transition temperature (Tg) of the resin, crosslinked resin particles, or uncrosslinked resin particles.

[0207] (Tensile impact strength) A 500 μm thick molded body (sheet-shaped molded body) prepared by the method described below was aged for 7 days under conditions of 23°C and 50% RH, and then punched out into a shape conforming to JIS K 71603 to prepare a test specimen. A tensile impact test was performed on the test specimen according to the method conforming to JIS K 7160 A method.

[0208] (Tensile elongation at break) A 200 μm thick molded body (film molded body) prepared by the method described below was used as a sample. The sample was aged for 7 days under conditions of 23°C and 50% RH. Thereafter, the tensile elongation at break of the sample was measured at 23°C at a test speed of 100 mm / min using a tensile tester (Shimadzu Corporation: EZ-LX 1kN) according to the method in accordance with JIS K 7127.

[0209] (Drop test of bottle-shaped molded body) The bottle-shaped molded body produced by the method described below and the water to be put into the bottle-shaped molded body were placed in a thermostatic chamber adjusted to each test temperature listed in the "Temperature (℃)" column of Table 6 for 12 hours or more for curing.

[0210] The bottle-shaped molded body was then filled with the amount of water specified in the "Weight of water (g)" column in Table 6 and the lid was closed. The bottle-shaped molded body containing water was then allowed to freely drop vertically from the height specified in the "Drop height (cm)" column in Table 6 up to 10 times in succession. The condition of the bottle-shaped molded body was checked immediately after each drop, and the test was terminated when any cracks or breaks occurred. The results are shown in Table 6. If the bottle did not break after 10 consecutive drops, it was judged to be "good," and if it did break, the number of tries before it broke was recorded.

[0211] (Charpy impact strength) The rectangular injection molded article produced by the method described below is notched with a V-notch and subjected to a Charpy impact test according to a method conforming to JIS K 7111. The Charpy impact strength of the injection molded article is measured in kJ / m. 2 Measurements were carried out.

[0212] (Elmendorf tear strength) For each of the thermoplastic resin compositions of the Examples and Comparative Examples, the Elmendorf tear strength was measured by the following methods (1) to (4): (1) The thermoplastic resin composition was molded into a film having a thickness of 40 μm or 110 μm to obtain a film molded product; (2) The film molded body obtained in step (1) was aged for 7 days under conditions of 23°C and 50% RH; (3) The tear strength (unit: N) of the film molded body after curing was measured by a method in accordance with JIS K7128-2; (4) The tear strength measured in (3) was divided by the thickness (unit: mm) of the film molded article to calculate the Elmendorf tear strength.

[0213] The measuring device used was a light load tear tester ("No. 2037 special specification machine" manufactured by Kumagai Riki Kogyo Co., Ltd.) having functions and structure conforming to the standard Elmendorf tear tester specified in JIS K7128-2.

[0214] In addition, the Elmendorf tear strength of each film molding was measured in both the MD direction (the flow direction of the molten resin (also the extrusion direction)) and the TD direction (the direction perpendicular to the flow of the molten resin (also the direction perpendicular to the extrusion direction)).

[0215] [Examples 1 to 19] (Raw material for cross-linked resin particles) <Uncrosslinked resin particles> Resin particles containing the following biodegradable resins were used as the uncrosslinked resin particles. PHA-1: Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate): Repeating unit composition; (3-hydroxybutyrate) / (3-hydroxyhexanoate)=72 / 28 (mol / mol), weight average molecular weight Mw; 500,000 to 1.5 million PHA-2: Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate): Repeating unit composition; (3-hydroxybutyrate) / (3-hydroxyhexanoate)=68 / 32 (mol / mol), weight average molecular weight Mw; 500,000 to 1.5 million PHA-3: Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate): Repeating unit composition; (3-hydroxybutyrate) / (3-hydroxyhexanoate)=75 / 25 (mol / mol), weight average molecular weight Mw; 600,000 to 1.5 million <Peroxide> PO-1: t-butyl peroxypivalate ("Luperox (registered trademark) 11" manufactured by Arkema Yoshitomi Co., Ltd., 1-hour half-life temperature: 76°C) PO-2: t-Butyl peroxy-2-ethylhexanoate ("Luperox (registered trademark) 26" manufactured by Arkema Yoshitomi Co., Ltd., 1-hour half-life temperature: 95°C) PO-3: t-Butylperoxy-2-ethylhexyl monocarbonate ("Perbutyl (registered trademark) E" manufactured by NOF Corporation, 1-hour half-life temperature: 119°C) PO-4: Di-sec-butyl peroxydicarbonate ("Luperox (registered trademark) 225" manufactured by Arkema Yoshitomi Co., Ltd., 1-hour half-life temperature: 69°C) <Polyfunctional compounds> CA-1: Allyl methacrylate · CA-2: Triallyl isocyanurate.

[0216] (Production of Crosslinked Resin Particles) The raw materials shown in Tables 1 and 2 were used in the amounts shown in Tables 1 and 2, and the crosslinked resin particles of Examples 1 to 19 were produced according to the procedures described below.

[0217] An aqueous dispersion of uncrosslinked resin particles dispersed in water (100 parts by weight of solids of uncrosslinked resin particles), 200 parts by weight of deionized water, a specified amount of peroxide, 2 parts by weight of sodium dioctyl sulfosuccinate, and a specified amount of polyfunctional compound were added to an autoclave or glass container equipped with a stirrer, a baffle, a nitrogen inlet, a nitrogen outlet, and a thermometer, and stirring was started at room temperature while the atmosphere inside the autoclave or glass container was replaced with nitrogen.

[0218] Thereafter, the contents in the autoclave or glass container were stirred at the temperature and for the time of impregnation conditions shown in Tables 1 and 2 to impregnate the inside of the uncrosslinked resin particles with the peroxide and the polyfunctional compound. Thereafter, the temperature of the contents in the autoclave or glass container was raised to the reaction temperature of the crosslinking conditions shown in Tables 1 and 2. After the temperature of the contents in the autoclave or glass container reached the reaction temperature, the uncrosslinked resin particles, the peroxide, and the polyfunctional compound were reacted at the reaction temperature for the reaction time of the crosslinking conditions shown in Tables 1 and 2 to obtain an aqueous dispersion in which crosslinked resin particles are dispersed in water.

[0219] The pH of the resulting aqueous dispersion was adjusted to pH 3.5 to 4, and then the dispersion was dried in an oven to obtain solidified crosslinked resin particles.

[0220] The glass transition temperature, volume average particle size and gel fraction of the crosslinked resin particles obtained in each Example were measured by the methods described above. The results are shown in Tables 1 and 2.

[0221] The glass transition temperature, volume average particle size, and gel fraction of the uncrosslinked resin particles before the crosslinking reaction were measured by the above-mentioned methods, and the results are shown in Table 1 as a reference example. The uncrosslinked resin particles or an aqueous dispersion thereof were used in Comparative Examples 2 to 4 and 8.

[0222] [Table 1]

[0223] [Table 2]

[0224] [Examples 20 to 42, Comparative Examples 1 to 4] (Raw material for thermoplastic resin composition) <Thermoplastic resin> PHBH (Kaneka Biodegradable Polymer PHBH (registered trademark), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate, repeating unit composition: (3-hydroxybutyrate) / (3-hydroxyhexanoate)=94.4 / 5.6 (mol / mol), weight average molecular weight Mw: 530,000, Tg 3°C) <Crosslinked resin particles> Crosslinked resin particles prepared in Examples 1 to 19 <Nucleating agent> Pentaerythritol (Neuriser P, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) <Lubricant> -Behenamide (BNT22H manufactured by Nippon Fine Chemicals).

[0225] (Examples 20 to 41 and Comparative Examples 1 to 4: Preparation of Thermoplastic Resin Compositions and Molded Articles) For each Example and Comparative Example, the thermoplastic resin, crosslinked resin particles (or uncrosslinked resin particles), crystal nucleating agent and lubricant shown in Tables 3 and 4 were mixed in the amounts shown in Tables 3 and 4 to obtain a mixture. The obtained mixture was kneaded for 180 seconds in a twin-screw small kneader (Xplore MC5 manufactured by DSM) with the barrel temperature heated to the temperature shown as "kneading temperature" in Tables 3 and 4 under the condition of a screw rotation speed of 100 rpm to obtain a kneaded product. The kneaded product was dried in a dryer at 80°C for 4 hours to sufficiently reduce the moisture content, thereby obtaining the thermoplastic resin compositions of Examples 20 to 41 and Comparative Examples 1 to 4. The thermoplastic resin compositions of Comparative Examples 1 to 4 and Examples 20 to 41 were press-molded to a predetermined thickness at 165°C to produce molded bodies.

[0226] The tensile impact strength of the obtained sheet-like molded product was measured by the above-mentioned method. The results are shown in Tables 3 and 4.

[0227] (Example 42: Preparation of thermoplastic resin composition and molded article) The aqueous dispersion of thermoplastic resin particles was mixed with the aqueous dispersion of crosslinked resin particles prepared in Example 11 in a weight ratio of 70 / 30% in terms of solid content to obtain a mixture. The pH of the obtained mixture was adjusted to 3.8, and then the mixture was dried in an oven to obtain a resin mixture.

[0228] The resin mixture, the nucleating agent and the lubricant were melt-kneaded under the same conditions as above to obtain a thermoplastic resin composition by the same method as above. The obtained thermoplastic resin composition was molded by the same method as above. The tensile impact strength of the obtained molded body was measured by the above-mentioned method. The results are shown in Table 4.

[0229] [Table 3]

[0230] [Table 4]

[0231] Tables 3 and 4 show that in Examples 20, 23, and 26 to 42, in which crosslinked resin particles were blended with a thermoplastic resin, the tensile impact strength values ​​were larger and impact resistance was improved compared to Comparative Example 1, which contained only a thermoplastic resin.

[0232] Furthermore, in Examples 20, 23, 26 to 29, 31, and 34 to 42, the tensile impact strength values ​​were larger than those of Comparative Example 3, which contained the same amount of uncrosslinked resin particles, and it is clear that the impact resistance was greatly improved by crosslinking. The same can be said from the comparison between Comparative Example 2 and Example 30, and the comparison between Comparative Example 4 and Example 32.

[0233] [Examples 43 to 48, Comparative Examples 5 to 8] (Raw material for thermoplastic resin composition) <Thermoplastic resin> · PLA (Polylactic acid: Natureworks 2003D) PBAT (Poly(butylene adipate-co-butylene terephthalate) (BASF Ecoflex C1200)) <Crosslinked resin particles> Crosslinked resin particles prepared in Examples 8, 11, 15, or 17, or uncrosslinked resin particles (PHA-1) (Preparation of Thermoplastic Resin Composition and Molded Article) For each Example and Comparative Example, the thermoplastic resin and the crosslinked resin particles or the uncrosslinked resin particles shown in Table 5 were mixed in the amounts shown in Table 5 to obtain a mixture. The obtained mixture was kneaded for 180 seconds in a twin-screw small kneader (Xplore MC5 manufactured by DSM) with the barrel temperature heated to 175°C and the screw rotation speed of 100 rpm to obtain a kneaded product. The kneaded product was dried in a dryer at 90°C for 2 hours to sufficiently reduce the moisture content, thereby obtaining the thermoplastic resin compositions of Examples 43 to 48 and Comparative Examples 5 to 8. The thermoplastic resin compositions of Examples 43 to 48 and Comparative Examples 5 to 8 were press-molded to a predetermined thickness at 170°C to produce molded bodies.

[0234] The tensile impact strength of the obtained sheet-like molded product was measured by the above-mentioned method, and the results are shown in Table 5.

[0235] [Table 5]

[0236] From Table 5, it can be seen that in Examples 43 to 48, in which crosslinked resin particles were blended with polylactic acid, a thermoplastic resin, the tensile impact strength values ​​were greater than those of Comparative Example 5, which contained only polylactic acid, and that the impact resistance of polylactic acid was improved by blending crosslinked resin particles.

[0237] Furthermore, in Examples 43 to 48, the tensile impact strength values ​​were larger than those of Comparative Examples 6 to 8, in which PBAT or uncrosslinked resin particles were blended instead of the crosslinked resin particles, and it is clear that the impact resistance of polylactic acid was improved by blending crosslinked resin particles. Comparing Comparative Example 7 with Example 44, the tensile impact strength when 10 parts by weight of crosslinked resin particles were blended was significantly higher than the tensile impact strength when 20 parts by weight of PBAT were blended, and it is also clear that the crosslinked resin particles have a high effect of improving impact resistance.

[0238] [Examples 49 and 50, Comparative Example 9: Object Drop Test] (Preparation of bottle-shaped molded body) The thermoplastic resin, crosslinked resin particles, crystal nucleating agent and lubricant used in Comparative Example 1, Examples 31 and 33 were used as raw materials to produce bottle-shaped molded articles of Comparative Example 9, Examples 49 and 50, respectively.

[0239] Specifically, the mixture of the thermoplastic resin, crosslinked resin particles, crystal nucleating agent and lubricant used in Comparative Example 1, Examples 31 and 33 was melt-kneaded in a twin-screw extruder (KZW15TWIN-45WG manufactured by Technobel Co., Ltd.) with the barrel temperature heated to 140 to 165°C and the screw rotation speed of 80 rpm to obtain a melt-kneaded product (mixture) (mixing step). The obtained melt-kneaded product was dried in a dryer at 80°C for 4 hours to sufficiently reduce the moisture content, thereby obtaining a thermoplastic resin composition of each Example and Comparative Example.

[0240] Then, using a 30MT injection molding machine (Si-30IV manufactured by Toyo Machinery & Metals Co., Ltd.), a bottle-shaped molded body with a volume of 328 ml, a thickness of 1.2 mm, an opening diameter of 66 mm, and a height of 1,010 mm was produced under conditions of a cylinder temperature of 140 to 165°C and a mold temperature of 40°C.

[0241] The bottle-shaped molded article thus obtained was subjected to an object drop test by the above-mentioned method. The results are shown in Table 6.

[0242] [Table 6]

[0243] From Table 6, it can be seen that in Comparative Example 9, in which no crosslinked resin particles were blended with the thermoplastic resin, the bottle-shaped molded body broke on the first drop at 23°C with 100 g of water and a drop height of 100 cm, whereas in Examples 49 and 50, in which crosslinked resin particles were blended, the water weight was increased to 200 g and the bottle-shaped molded body did not break even after 10 drops.

[0244] Furthermore, under conditions of 2°C, 100g of water weight, and 100cm drop height, Comparative Example 9, which does not contain crosslinked resin particles, broke on the second drop, whereas Examples 49 and 50, which contain crosslinked resin particles, did not break even after 10 drops. Also, Example 50 did not break even after 10 drops when the water weight was increased to 200g under the same conditions.

[0245] [Examples 51 to 57] (Raw material for cross-linked resin particles) <Uncrosslinked resin particles> Resin particles containing the following biodegradable resins were used as the uncrosslinked resin particles. PHA-1: (Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate), repeating unit composition: (3-hydroxybutyrate) / (3-hydroxyhexanoate)=72 / 28 (mol / mol), weight average molecular weight Mw: 500,000 to 1.5 million) PHA-4: (Poly(3-hydroxybutyrate-co-4-hydroxybutyrate), repeating unit composition: (3-hydroxybutyrate) / (4-hydroxybutyrate)=65 / 35 (mol / mol), weight average molecular weight Mw: 400,000 to 1.5 million) PBAT: BASF Ecoflex® F blend C1200 PBSA: Mitsubishi Chemical Corporation, FD92 PCL: Ingevity, Capa6800 PHA / PCL: a mixture of 50% by weight of the PHA-1 and 50% by weight of the PCL (total 100% by weight). PBS: Showa Denko Co., Ltd., "Bionolle (registered trademark)" <Peroxide> PO-4: Di(secondary butyl) peroxydicarbonate ("Luperox (registered trademark) 225" manufactured by Arkema Yoshitomi Co., Ltd., 1-hour half-life temperature: 69°C) <Polyfunctional compounds> · Triallyl isocyanurate.

[0246] (Production of Crosslinked Resin Particles) The crosslinked resin particles of Examples 51 to 57 were produced according to the procedure described below.

[0247] Each of the resins listed in Table 7 was completely dissolved in chloroform to a concentration of 10%, to obtain raw material 1. Surfactin (manufactured by Kaneka Corporation) and glycerin were mixed in a ratio of 6 / 94% by weight, and the mixture was stirred for 5 to 10 minutes to obtain raw material 2. Raw materials 1 and 2 were weighed out to a ratio of 86 / 14% by weight. Raw material 1 was slowly dropped into raw material 2 while stirring raw material 2, and after the entire amount of raw material 1 was dropped, the mixture was stirred for another 30 minutes. Next, 100% by weight of deionized water was added to the mixture obtained, based on the total weight of raw materials 1 and 2 (100% by weight), to obtain a dispersion of resin particles. After that, the dispersion was stirred at 65°C for about 30 minutes, and the chloroform remaining in the dispersion was removed from the dispersion, to obtain an aqueous dispersion of uncrosslinked resin particles.

[0248] Into a glass vessel equipped with a stirrer, a baffle, a nitrogen inlet, a nitrogen outlet, and a thermometer, an aqueous dispersion in which uncrosslinked resin particles are dispersed in water (100 parts by weight in terms of solid content), 200 parts by weight of deionized water, the amount of peroxide shown in Table 7, 2 parts by weight of sodium dioctyl sulfosuccinate, and the amount of polyfunctional compound shown in Table 7 were added to prepare an aqueous dispersion. Next, stirring of the obtained aqueous dispersion was started at room temperature, and at the same time, the atmosphere in the glass vessel was replaced with nitrogen.

[0249] Thereafter, the content (aqueous dispersion) of the glass container was stirred at room temperature for 1 hour to allow the peroxide and the polyfunctional compound to be impregnated into the interior of the uncrosslinked resin particles.

[0250] Thereafter, the aqueous dispersion was heated to a temperature shown in the column of crosslinking temperature under crosslinking conditions in Table 7 to decompose the peroxide and crosslink the biodegradable resin particles. After the crosslinking temperature was reached, the aqueous dispersion was maintained at the crosslinking temperature for the time shown in the column of crosslinking time under crosslinking conditions in Table 7 to sufficiently crosslink the biodegradable resin particles, thereby obtaining an aqueous dispersion in which crosslinked resin particles are dispersed in water.

[0251] After adjusting the pH of the aqueous dispersion, the aqueous dispersion was dried in an oven. The obtained solid matter was washed several times with ionized water to wash away the glycerin remaining in the solid matter of the crosslinked resin particles. The washed crosslinked resin particles were dried again in an oven to obtain solidified crosslinked resin particles. The obtained crosslinked resin particles can also be considered as a modifier for thermoplastic resins.

[0252] The median diameter, gel fraction, glass transition temperature, and solubility in chloroform of the crosslinked resin particles obtained in each Example were measured by the above-mentioned methods. The results are shown in Table 7.

[0253] [Table 7]

[0254] [Examples 58 to 63, Comparative Example 10] (Raw material for thermoplastic resin composition) <Thermoplastic resin> P3HB3HH (Kaneka Corporation, Kaneka Biodegradable Polymer PHBH (registered trademark), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate, repeating unit composition: (3-hydroxybutyrate) / (3-hydroxyhexanoate)=94.4 / 5.6 (mol / mol), weight average molecular weight Mw: 530,000, Tg 3°C) <Crosslinked resin particles> Crosslinked resin particles prepared in Examples 51 to 57 <Nucleating agent> Pentaerythritol (Neuriser P, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) <Lubricant> -Behenamide (BNT22H manufactured by Nippon Fine Chemicals).

[0255] (Preparation of Thermoplastic Resin Composition and Molded Article) For each Example, the thermoplastic resin, crosslinked resin particles, crystal nucleating agent, and lubricant shown in Table 8 were mixed in the amounts shown in Table 8 to obtain a mixture. The obtained mixture was melt-kneaded for 180 seconds in a twin-screw small kneader (Xplore MC5 manufactured by DSM) with the barrel temperature heated to 175° C. and the screw rotation speed at 100 rpm to obtain a melt-kneaded product. The obtained melt-kneaded product was dried in a dryer at 80° C. for 4 hours to sufficiently reduce the moisture content, thereby obtaining the thermoplastic resin compositions of Comparative Example 10 and Examples 58 to 63. The thermoplastic resin compositions of Comparative Example 10 and each Example were press-molded to a predetermined thickness at 165° C. to produce molded products (film molded products and sheet molded products).

[0256] The tensile elongation at break was measured by the above-mentioned method for the molded articles of Comparative Example 10 and Examples 58 to 63. The tensile impact strength was measured by the above-mentioned method for the molded articles of Comparative Example 10 and Example 61. The results are shown in Table 8.

[0257] [Table 8]

[0258] From Table 8, it can be seen that the molded bodies of the examples to which crosslinked resin particles were added exhibited good tensile elongation and tensile impact strength compared to the molded bodies of the comparative examples to which crosslinked resin particles were not added.

[0259] [Examples 64, 65, Comparative Example 11: Measurement of Charpy impact strength] (Preparation of injection molded body) The thermoplastic resin, crosslinked resin particles, crystal nucleating agent and lubricant used in Comparative Example 1, Examples 31 and 33 were used as raw materials in the same amounts as in Comparative Example 1, Examples 31 and 33. The mixture was melt-kneaded in a twin-screw extruder (KZW15TWIN-45WG manufactured by Technobel Co., Ltd.) with a barrel temperature of 140 to 165 ° C. and a screw rotation speed of 80 rpm to obtain a melt-kneaded product (mixture). The obtained kneaded product was dried under conditions of a drying temperature of 80 ° C. and a drying time of 4 hours, and the moisture content was sufficiently reduced to obtain a thermoplastic resin composition. The obtained thermoplastic resin composition was molded in a 15MT injection molding machine (Si-15III manufactured by Toyo Machinery and Metal Co., Ltd.) under conditions of a cylinder temperature of 120 to 155 ° C. and a mold temperature of 40 ° C. The shape of the cavity in the closed state of the mold was a rectangular parallelepiped with a length of 80 mm, a width of 4 mm and a thickness of 10 mm. As a result of the molding, a rectangular parallelepiped test piece having the same shape as the cavity, i.e., a length of 80 mm, a width of 4 mm, and a thickness of 10 mm, was obtained inside the mold. The rectangular parallelepiped test piece was removed from the mold and then cured for 7 days under conditions of 23°C and 50% RH to obtain a rectangular parallelepiped injection molded body. In this manner, the rectangular parallelepiped injection molded bodies of Comparative Example 11, Examples 64, and 65 were produced from the raw materials used in Comparative Example 1, Examples 31, and 33, respectively.

[0260] The Charpy impact strength of the resulting rectangular injection molded articles was measured by the method described above. The results are shown in Table 9.

[0261] [Table 9]

[0262] As shown in Table 9, the injection molded articles of Examples 64 and 65 obtained by molding thermoplastic resin compositions in which crosslinked resin particles were blended with a thermoplastic resin had higher Charpy impact strength than the injection molded article of Comparative Example 11 in which no crosslinked resin particles were blended. This demonstrates that the injection molded article in which crosslinked resin particles were blended with a thermoplastic resin has excellent impact resistance.

[0263] [Examples 66 to 68 and Comparative Example 12: Measurement of Elmendorf tear strength] The thermoplastic resins, crosslinked resin particles, crystal nucleating agent, and lubricant used in Comparative Example 1, and Examples 31, 33, and 41 were used as raw materials in the amounts shown in Table 10, and kneaded in the same manner as in the Comparative Examples and Examples to obtain kneaded products. The kneaded products obtained were dried under conditions of a drying temperature of 80°C and a drying time of 4 hours to sufficiently reduce the moisture content, thereby obtaining the thermoplastic resin compositions of Examples 66 to 68 and Comparative Example 12.

[0264] The Elmendorf tear strength of the resulting thermoplastic resin composition was measured by the method described above, and the results are shown in Table 10.

[0265] [Table 10]

[0266] From Table 10, it can be seen that in Examples 66 to 68 in which crosslinked resin particles were blended with a thermoplastic resin, the Elmendorf tear strength values ​​were greater than in Comparative Example 12 which contained only a thermoplastic resin. [Industrial Applicability]

[0267] According to one embodiment of the present invention, there is provided a method for producing crosslinked resin particles that can provide crosslinked resin particles having biodegradability and excellent impact resistance, tensile properties, and tear resistance. Therefore, one embodiment of the present invention can be suitably used as a modifier, spacer, antiblocking agent, matting agent, etc. for thermoplastic resins.

Claims

1. Contains a biodegradable resin (A), Crosslinked resin particles having a gel fraction of 50% or more, a volume average particle size of 0.10 μm to 10.00 μm or a median size of 0.10 μm to 10.00 μm, and a glass transition temperature of 0° C. or lower.

2. The crosslinked resin particles according to claim 1 , wherein the biodegradable resin (A) is a polyhydroxyalkanoate-based resin.

3. 3. The crosslinked resin particles according to claim 2, wherein the polyhydroxyalkanoate resin is a poly(3-hydroxyalkanoate) resin.

4. 2. The crosslinked resin particles of claim 1, wherein the crosslinked resin particles are crosslinked using a peroxide.

5. 5. The crosslinked resin particles according to claim 4, wherein the crosslinked resin particles are crosslinked in the presence of the peroxide and a polyfunctional compound.

6. 2. The crosslinked resin particles of claim 1, wherein the crosslinked resin particles are non-foamed.

7. 2. The crosslinked resin particles according to claim 1, wherein the proportion of the biodegradable resin (A) in the crosslinked resin particles is 80% by weight or more.

8. 2. The crosslinked resin particles according to claim 1, wherein the gel fraction is from 70% to 100%.

9. 9. An aqueous dispersion in which the crosslinked resin particles according to claim 1 are dispersed in an aqueous medium.

10. Thermoplastic resin, and A thermoplastic resin composition comprising the crosslinked resin particles according to any one of claims 1 to 8.

11. The thermoplastic resin composition according to claim 10 , wherein the thermoplastic resin comprises a biodegradable resin (B).

12. The thermoplastic resin composition according to claim 11 , wherein the biodegradable resin (B) comprises a polyester-based resin.

13. The thermoplastic resin composition according to claim 10, further comprising a crystal nucleating agent and / or a lubricant.

14. A molded article obtained by molding the thermoplastic resin composition according to claim 10.

15. The molded article according to claim 14, wherein the molded article is a sheet molded article, a film molded article, a blow molded article, an extrusion molded article, a vacuum molded article, or an injection molded article.

16. Contains crosslinked resin particles, The crosslinked resin particles contain a biodegradable resin (A), A modifier for thermoplastic resins, having a gel fraction of 50% or more, a volume average particle size of 0.10 μm to 10.00 μm or a median size of 0.10 μm to 10.00 μm, and a glass transition temperature of 0° C. or lower.

17. A method for producing the crosslinked resin particles according to any one of claims 1 to 8, comprising the steps of: A production method comprising a step of crosslinking biodegradable resin (A) particles in an aqueous dispersion of the biodegradable resin (A) particles in the presence of a peroxide.

Citation Information

Patent Citations

  • Vinylic crosslinked resin particle, its manufacturing method and use thereof

    JP2003082191A

  • Matt acrylic resin film having improved design flexibility after being coated

    JP2009056770A

  • Poly(3-hydroxyalkanoate) resin composition

    WO2019022008A1